Adaptive management: where are we now? - Rist, Lucy; Campbell, Bruce M.; Frost, Peter (Environmental Conservation, 2013)
Adaptive management (AM) emerged in the literature in the mid-1970s in response both to a realization of the extent of uncertainty involved in management, and a frustration with attempts to use modelling to integrate knowledge and make predictions. The term has since become increasingly widely used in scientific articles, policy documents and management plans, but both understanding and application of the concept is mixed. This paper reviews recent literature from conservation and natural resource management journals to assess diversity in how the term is used, highlight ambiguities and consider how the concept might be further assessed. AM is currently being used to describe many different management contexts, scales and locations. Few authors define the term explicitly or describe how it offers a means to improve management outcomes in their specific management context. Many do not adhere to the idea as it was originally conceived, despite citing seminal work. Significant confusion exists over the distinction between active and passive approaches. Over half of the studies reporting to implement AM claimed to have done so successfully, yet none quantified specific benefits, or costs, in relation to possible alternatives. Similarly those studies reporting to assess the approach did so only in relation to specific models and their parameterizations; none assessed the benefits or costs of AM in the field. AM is regarded by some as an effective and well-established framework to support the management of natural resources, yet by others as a concept difficult to realize and fraught with implementation challenges; neither of these observations is wholly accurate. From a scientific and technical perspective many practical questions remain; in particular real-world assessments of the value of experimentation within a management framework, as well as of identified challenges and pathologies, are needed. Further discussion and systematic assessment of the approach is required, together with greater attention to its definition and description, enabling the assessment of new approaches to managing uncertainty, and AM itself.
Keywords: Adaptive Management; Decision making; Natural resource management; conservation; experimental management; uncertainty

Adaptive management intentions with a reality of evaluation: Getting science back into policy - Hasselman, Lyndal (Environmental Science & Policy, 2017)
In Australia’s Murray-Darling Basin water reform has been contentious as government attempts to reconcile historical over allocation of water to irrigation with the use of water for environmental outcomes. However, in many aspects, scientific knowledge of the environment is either imperfect, incomplete or environmental responses are unpredictable, with this uncertainty preventing definitive policy and closure of political arguments. In response to uncertainty and knowledge gaps, adaptive management has been written into the legislation, along with provisions for periodic evaluation. This research ascertains how adaptive management is understood by policy makers, with this indicative of future implementation of adaptive management. The way in which adaptive management is constructed by policy makers is determined through legislation, public speeches, government reports and semi-structured interviews. The findings demonstrate that adaptive management has been subsumed by evaluation. The loss of adaptive management as a distinct concept is seen as a loss of science and discovery from the policy process, with the dominance of evaluation discussed as limiting innovation and reinforcing a ‘muddling through’ of policy.
Keywords: Accountability; Adaptive Management; Evaluation; Science; Uncertainty

Adaptive Management: From More Talk to Real Action - Williams, Byron K.; Brown, Eleanor D. (Environmental Management, 2014)
The challenges currently facing resource managers are large-scale and complex, and demand new approaches to balance development and conservation goals. One approach that shows considerable promise for addressing these challenges is adaptive management, which by now is broadly seen as a natural, intuitive, and potentially effective way to address decision-making in the face of uncertainties. Yet the concept of adaptive management continues to evolve, and its record of success remains limited. In this article, we present an operational framework for adaptive decision-making, and describe the challenges and opportunities in applying it to real-world problems. We discuss the key elements required for adaptive decision-making, and their integration into an iterative process that highlights and distinguishes technical and social learning. We illustrate the elements and processes of the framework with some successful on-the-ground examples of natural resource management. Finally, we address some of the difficulties in applying learning-based management, and finish with a discussion of future directions and strategic challenges.
Keywords: IMPORTANT

Webinar: Operationalizing Adaptive Management: What it takes. Why it matters. - Mercy Corps (Mercy Corps, 2015)
Development actors increasingly agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. A growing body of evidence supports this claim. But what does adaptive management look like in practice? What does it require of managers and donors to make happen? How can we reconfigure incentives and success metrics to support adaptation, while remaining compliant?

Managing to Adapt: Analysing adaptive management for planning, monitoring, evaluation, and learning - Desai, Harsh; Maneo, Gabriele; Pellfolk, Erica; Schlingheider, Annika (Oxfam Research Reports, 2018)
Adaptive management is at the heart of ‘Doing Development Differently’. It emerges from stakeholders’ calls for development programmes to be more flexible and responsive to their contexts. Whether it becomes a mainstreamed practice depends on how much it is

Technical challenges in the application of adaptive management - Williams, Byron K.; Brown, Eleanor D. (Biological Conservation, 2016)
Adaptive management is an approach for simultaneously managing and learning about natural resources, by acknowledging uncertainty and seeking to reduce it through the process of management itself. Adaptive decision making can be applied to pressing issues in conservation biology such as species reintroduction, disease and invasive species control, and habitat restoration, as well as to management of natural resources in general. After briefly outlining a framework and process for adaptive management, we focus on an overview of the key technical issues related to problem framing and the ability of resource managers to learn from their experience. These technical issues include the treatment of uncertainty and its propagation over time; nonstationarity in long-term environmental trends; the applicability of adaptive management across scales; requirements for models and management alternatives that promote learning; the value of the information produced with adaptive management; the challenge to management of uncertainty and surprise; and institutional (social) learning. To accommodate these and other challenges that are now coming into focus, the learning-based approach of adaptive management will need to be adjusted and expanded in the future.
Keywords: Adaptive Management; Learning; Nonstationarity; Resilience; Uncertainty; Value of information

Managing Complexity: Adaptive Management at Mercy Corps - Mercy Corps (2015)
Managing Complexity: Adaptive management at Mercy Corps

Management not models: adaptability, responsiveness, and a few lessons from football - Maclay, Christopher (Development in Practice, 2015)
Despite a swathe of critiques of logframes and other blueprint approaches to development over the last 30 years, most aid infrastructure continues to concentrate on the design and subsequent implementation of closed models. This article does not propose an alternative to blueprints, but challenges the inflexibility of their implementation, which is inadequate given the complex nature of social change. It proposes a supplementary management and learning approach which enables implementers to be dynamic, adaptive, and responsive to problems and opportunities. Emphasising the role of donors, the paper presents a case study of one donor-led programme in Bangladesh doing just this.

Passive and active adaptive management: Approaches and an example - Williams, Byron (Journal of Environmental Management, 2010)
Adaptive management is a framework for resource conservation that promotes iterative learning-based decision making. Yet there remains considerable confusion about what adaptive management entails, and how to actually make resource decisions adaptively. A key but somewhat ambiguous distinction in adaptive management is between active and passive forms of adaptive decision making. The objective of this paper is to illustrate some approaches to active and passive adaptive management with a simple example involving the drawdown of water impoundments on a wildlife refuge. The approaches are illustrated for the drawdown example, and contrasted in terms of objectives, costs, and potential learning rates. Some key challenges to the actual practice of AM are discussed, and tradeoffs between implementation costs and long-term benefits are highlighted.

Bringing adaptive management to life: Insights from practice - Arora, Anmol; Gogoi, Elizabeth; Joy, Divya; Kumar, Pankaj; Luthra, Rajni; Pal, Uma; Pervaiz, Arif (Oxford Policy Management, 2019)
The increasing popularity of adaptive programmes in the development sector in the past decade is partly a response to the complex and interconnected challenges facing many developing countries, including the impacts of climate change. The pathway to adapting to climate change is unknown, and there are many deep-rooted institutional, political, economic and social barriers. Adaptive programmes provide the flexibility to allow those delivering the technical assistance to support governments to experiment with different entry points and to adapt or change course when some are not successful. The Action on Climate Today (ACT) programme is a five-year adaptive programme that aims to strengthen systems of planning and delivery for adaptation to climate change in South Asia. As the programme draws to a close, this Learning Paper reflects on some of the major lessons learnt on the challenges and opportunities of using an adaptive programme management approach to support governments to adapt to climate change. The authors are members of the ACT implementation team, representing the management, operational and technical teams, from across different locations. The paper therefore reflects their first-hand account of the reality of implementing adaptive programmes. The paper sets out a framework for the essential ingredients of an adaptive programme management approach. These include a set of essential core principles: an evolving theory of change; a locally led and politically savvy delivery approach; experimentation and learning; and stakeholder alignment. It also includes two sets of essential resources required: management flexibility and adequate financial resources. The paper then provides learning from ACT on how to operationalise these core principles and mobilise the necessary resources. It gives detailed examples of challenges faced by ACT with regard to each component of the framework, and how the programme has overcome them, as well as retrospective reflections of additional actions the programme could have taken. A set of case studies unpacks how adaptive programme management has been operationalised in practice in particular locations. The authors are confident that the impact ACT has had owes in large part to it being an adaptive programme. The programme’s flexibility, decentralised structure and strong emphasis on learning have meant the team has been able to respond to opportunities as they have emerged and to invest time and resources where there was most potential for impact. However, this paper is also honest about the challenges ACT has faced as an adaptively managed programme. The paper therefore concludes with a set of lessons learnt from ACT for the benefit of others designing and delivering adaptive programmes on climate change and other issues.

The relationship between adaptive management of social-ecological systems and law: a systematic review - Frohlich, Miguel F.; Jacobson, Chris; Fidelman, Pedro; Smith, Timothy F. (Ecology and Society, 2018)
Adaptive management has been considered a valuable approach for managing social-ecological systems involving high levels of complexity and uncertainty. However, many obstacles still hamper its implementation. Law is often seen as a barrier for moving adaptive management beyond theory, although there has been no synthesis on the challenges of legal constraints or how to overcome them. We contribute to filling this knowledge gap by providing a systematic review of the peer-reviewed literature on the relationship between adaptive management and law in relation to social-ecological systems. We analyze how the scholarship defines the concept of adaptive management, identifies the legal barriers to adaptive management, and the legal strategies suggested for enabling this approach. Research efforts in this domain are still highly geographically concentrated in the United States of America, unveiling gaps concerning the analysis of other legal jurisdictions. Overall, our results show that more flexible legal frameworks can allow for adaptive management without undermining the role of law in providing stability to social interactions. Achieving this balance will likely require the reform of existing laws, regulations, and other legal instruments. Legal reforms can facilitate the emergence of adaptive governance, with the potential to support not only adaptive management implementation but also to make law itself more adaptive.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Pyoe Pin, Myanmar - Christie, Angela; Green, Duncan (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches in aid programming in a fragile, conflict and violence-affected setting (FCVAS), namely Myanmar. A combination of desk review and field research has been used to examine some of the assertions around the ‘adaptive management’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blue-print and linear project plans. This paper explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for promoting empowerment and accountability in such ‘messy places’. This case study focuses on Pyoe Pin (‘Young Shoots’), a DFID-funded, British Council managed governance programme, which has been running since 2007.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adapting to Learn and Learning to Adapt: Practical Insights from International Development Projects - Brinkerhoff, Derick W.; Frazer, Sarah; McGregor, Lisa (RTI Press, 2018)
Adaptive programming and management principles focused on learning, experimentation, and evidence-based decision making are gaining traction with donor agencies and implementing partners in international development. Adaptation calls for using learning to inform adjustments during project implementation. This requires information gathering methods that promote reflection, learning, and adaption, beyond reporting on pre-specified data. A focus on adaptation changes traditional thinking about program cycle. It both erases the boundaries between design, implementation, and evaluation and reframes thinking to consider the complexity of development problems and nonlinear change pathways.Supportive management structures and processes are crucial for fostering adaptive management. Implementers and donors are experimenting with how procurement, contracting, work planning, and reporting can be modified to foster adaptive programming. Well-designed monitoring, evaluation, and learning systems can go beyond meeting accountability and reporting requirements to produce data and learning for evidence-based decision making and adaptive management. It is important to continue experimenting and learning to integrate adaptive programming and management into the operational policies and practices of donor agencies, country partners, and implementers. We need to devote ongoing effort to build the evidence base for the contributions of adaptive management to achieving international development results.

Using adaptive processes and adverse outcome pathways to develop meaningful, robust, and actionable environmental monitoring programs - Arciszewski, Tim J.; Munkittrick, Kelly R.; Scrimgeour, Garry J.; Dubé, Monique G.; Wrona, Fred J.; Hazewinkel, Rod R. (Integrated Environmental Assessment and Management, 2017)
The primary goals of environmental monitoring are to indicate whether unexpected changes related to development are occurring in the physical, chemical, and biological attributes of ecosystems and to inform meaningful management intervention. Although achieving these objectives is conceptually simple, varying scientific and social challenges often result in their breakdown. Conceptualizing, designing, and operating programs that better delineate monitoring, management, and risk assessment processes supported by hypothesis-driven approaches, strong inference, and adverse outcome pathways can overcome many of the challenges. Generally, a robust monitoring program is characterized by hypothesis-driven questions associated with potential adverse outcomes and feedback loops informed by data. Specifically, key and basic features are predictions of future observations (triggers) and mechanisms to respond to success or failure of those predictions (tiers). The adaptive processes accelerate or decelerate the effort to highlight and overcome ignorance while preventing the potentially unnecessary escalation of unguided monitoring and management. The deployment of the mutually reinforcing components can allow for more meaningful and actionable monitoring programs that better associate activities with consequences. Integr Environ Assess Manag 2017;13:877–891. © 2017 The Authors. Integrated Environmental Assessment and Management Published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC)
Keywords: Adaptive monitoring; Environmental management; Environmental monitoring; Tier; Trigger

Learning to ADAPT: monitoring and evaluation approaches in climate change adaptation and disaster risk reduction – challenges, gaps and ways forward - Silva Villanueva, Paula (SRC Discussion Paper, 2011)
This working paper is a methodological contribution to the emerging debate on monitoring and evaluation (M&E) in the context of climate change adaptationand disaster risk reduction. Effectively managing disaster risk is critical for adapting to the impacts of climate change, however disasters risk reduction M&E practice may be limited in capturing progress towards adaptation. The unique nature of adaptation to climate change calls for experience-based learning M&E processes for discovering the key insights into adaptive capacity and its links to adaptation processes, and to risk and vulnerability reduction at large. The ADAPT guiding principles and indicators set the foundations towards this end.

Learning to Adapt: Exploring Knowledge, Information and Data for Adaptive Programmes and Policies - Workshop Summary Report - fhi360 (IDS, 2015)
Adaptive management is increasingly seen as critical capability for development programmes and policies that are more effective, efficient, relevant and sustainable. There is increasing recognition that such work requires significant changes to the organizational structures, management processes, accountability and performance cultures and indivi

Participatory adaptive management leads to environmental learning outcomes extending beyond the sphere of science - Fujitani, Marie; McFall, Andrew; Randler, Christoph; Arlinghaus, Robert (Science Advances, 2017)
Resolving uncertainties in managed social-ecological systems requires adaptive experimentation at whole-ecosystem levels. However, whether participatory adaptive management fosters ecological understanding among stakeholders beyond the sphere of science is unknown. We experimentally involved members of German angling clubs (n = 181 in workshops, n = 2483 in total) engaged in self-governance of freshwater fisheries resources in a large-scale ecological experiment of active adaptive management of fish stocking, which constitutes a controversial management practice for biodiversity and ecosystem functioning when conducted inappropriately. The collaborative ecological experiments spanned several years and manipulated fish densities in 24 lakes with two species. In parallel, we experimentally compared changes in ecological knowledge and antecedents of proenvironmental behavior in stakeholders and managers who were members of a participatory adaptive management treatment group, with those receiving only a standard lecture, relative to placebo controls. Using a within-subjects pretest-posttest control design, changes in ecological knowledge, environmental beliefs, attitudes, norms, and behavioral intentions were evaluated. Participants in adaptive management retained more knowledge of ecological topics after a period of 8 months compared to those receiving a standard lecture, both relative to controls. Involvement in adaptive management was also the only treatment that altered personal norms and beliefs related to stocking. Critically, only the stakeholders who participated in adaptive management reduced their behavioral intentions to engage in fish stocking in the future. Adaptive management is essential for robust ecological knowledge, and we show that involving stakeholders in adaptive management experiments is a powerful tool to enhance ecological literacy and build environmental capacity to move toward sustainability. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders. Participatory active adaptive management leads to far-reaching environmental learning outcomes in stakeholders.

Global Learning for Adaptive Management (GLAM) - DFID (DFID Development Tracker, 2016)
To improve the value for money and impact of development interventions by promoting the use of better monitoring, evaluation and learning strategies that support development programmes to gather and respond to emergent evidence on the effects of interventions, as well as changes in the development context. The Global Learning for Adpative Management programme will make available technical assistance to DFID, USAID and partners to develop this ‘adaptive management’ approach, as well as build an evidence base to understand links between the use of adaptive management and more effective, efficient, relevant and sustainable development interventions.

Navigating complexity: Adaptive management in the Northern Karamoja Growth, Health & Governance program - Allana, Amir (MercyCorps, 2014)
Development actors increasing agree that managing programs adaptively – especially complex interventions – can improve their effectiveness. But what does adaptive management look like in practice?
Keywords: IMPORTANT; Practice

Making adaptive rigour work - Principles and practices for strenghening monitoring, evaluation and learning for adaptive management - Ramalingam, Ben; Wild, Leni; Buffardi, Anne L (ODI/GLAM, 2019)
Adaptive programmes can be accountable, rigorous and high quality in how they use evidence by taking an ’adaptive rigour’ approach. Core development and humanitarian challenges are complex, and require processes of testing, learning and iteration to find solutions – adaptive management offers one approach for this. Yet large bureaucracies and development organisations can have low tolerance for experimentation and learning, and adaptive management can be viewed as an excuse for ‘making things up as you go along’. This briefing from the Global Learning for Adaptive Management (GLAM) initiative argues that adaptive programmes can be accountable, rigorous and high quality in how they use evidence – but this requires rethinking some key assumptions about how they are practised. The paper sets out three key elements of an ‘adaptive rigour’ approach: - Strengthening the quality of monitoring, evaluation and learning data and systems. - Ensuring appropriate investment in monitoring, evaluation and learning across the programme cycle. - Strengthening capacities and incentives to ensure the effective use of evidence and learning as part of decision-making, leading ultimately to improved effectiveness.

Portfolios of Agile Projects: A Complex Adaptive Systems’ Agent Perspective - Sweetman, Roger; Conboy, Kieran (Project Management Journal, 2018)
While agile approaches can be extremely effective at a project level, they can impose significant complexity and a need for adaptiveness at the project portfolio level. While this has proven to be highly problematic, there is little research on how to manage a set of agile projects at the project portfolio level. What limited research that does exist often assumes that portfolio-level agility can be achieved by simply scaling project level agile approaches such as Scrum. This study uses a complex adaptive systems lens, focusing specifically on the properties of projects as agents in a complex adaptive portfolio to critically appraise current thinking on portfolio management in an agile context. We then draw on a set of 30 expert interviews to develop 16 complex adaptive systems (CAS)-based propositions as to how portfolios of agile projects can be managed effectively. We also outline an agenda for future research and discuss the differences between a CAS-based approach to portfolio management and traditional approaches.

Putting learning at the centre: Adaptive development programming in practice - Valters, Craig; Cummings, Clare; Nixon, Hamish (ODI, 2016)
Adaptive programming suggests, at a minimum, that development actors react and respond to changes in the political and socio-economic operating environment. It emphasises learning and the development practitioner is encouraged to adjust their actions to find workable solutions to problems that they may face. Being prepared to react to change may seem like common sense – and indeed it is. However much development thinking and practice remains stuck in a linear planning model which discourages learning and adaptation, in part because projects are seen as ‘closed, controllable and unchanging systems’ (Mosse, 1998: 5). This paper critically engages with this problem and makes clear why and how learning needs to be at the centre of adaptive development programming. It begins by clarifying why and what kind of learning matters for adaptive programming. The paper then turns its focus to how strategies and approaches applied throughout a programme’s conception, design, management and M&E can enable it to continually learn and adapt.
Keywords: IMPORTANT

Toybox's Adaptive Management in Practice - Malcolm, Emily (Toybox, 2017)
At Toybox, we understand ‘Adaptive Management’ as a broad innovative and learning approach that involves the whole organisation, our partners and funders. ‘Adaptive Programming’ of projects is part of this approach which is greatly enhanced by the Adaptive Management of all actors, including communities and children in the projects. Over the last few years Toybox have been piloting Adaptive Programming with our partners across Latin America, Africa and Asia to support children in street situations. This project has been developed within the wider context of an organisation which is focused on innovation and learning, therefore enabling Adaptive Management to become mainstream within the organisation. This paper captures the experiences and learnings of Toybox to our newly implemented Adaptive Programming approach, through the lens of a small-sized UK-based organisation working with local organisations internationally. This paper explains our learnings, inclusive of why we believe Adaptive Management is important to Toybox and how the organisation has embraced this new approach.

Adaptive Management Practice in the UK Government - The MUVA case - HLS (Human Learning Systems, 2019)
Case study about the MUVA programme in Mozambique. (Maybe it "misses the point of AP which is not learning for learning. Is learning for impact. The word impact doesn’t even come up once!") Adaptive Management programming within the Foreign & Commonwealth Development Office demonstrates that the UK Government has examples of optimising for learning within its existing management practice. However, currently, the adaptive management practices are unhelpfully framed by an approach which limits both their effectiveness and scope. The programmes use learning as their metastrategy. They succeed in connecting practicebased learning with strategic learning, and make a shift towards reframing accountability as accountability for learning. This learning strategy is enabled by funding and contract management arrangements which prioritise learning. Both at macro-level of programme management and micro level of de-risking experimentation and enabling necessary failure by decoupling people’s job security from potential failure.

Adaptive Management Leaders Launch Practical Adaptation Network (PAN) - Labs, Feedback (FeedbackLabs, 2016)
Great things can happen at the frontier of theory and practice. When Feedback Labs worked with USAID’s Global Development Lab to bring together leaders in adaptive management at the White House on June 15th, we were pleased that we were able to move past the ongoing conceptual conversations toward discussing what we could do in concrete terms to implement adaptive management in practice.

SAVI Approach Paper 11: Managing and Staffing an Adaptive Citizen Engagement Programme - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme putting learning and adaptation at the centre of all decision-making. In relation to management and staffing SAVI has established the following approaches to facilitate this: – An adaptive approach to programme management: Full time strategic technical leadership, that works closely with and complements...

Adaptive Management in Practice: a case study on the Prospects program - Maclay, Chris (Prospects practice paper, 1, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptive management in aid programmes (BEAM Exchange, 2014)
Aid works better – especially in complex and conflict-affected environments – when there is scope to trial and adapt programme strategies. So argues Amir Allana in Navigating Complexity, a case study of Northern Karamoja's Growth, Health and Governance (GHG) Programme that is adopting an 'adaptive management' approach. This BEAM Exchange webinar invited Amir, Tim Sparkman and Peter Roggekamp to discuss lessons from their work in Uganda and Cambodia. What does adaptive management look like in practice? And what does it require of managers and funders to make it happen? Tim and Peter share their experiences of applying adaptive management techniques to the Growth, Health and Governance Programme and the Cambodia Agricultural Value Chain Program (CAVAC). Amir highlight insights from the Navigating Complexity report, including the importance of office culture, consistent management signals, and the role of supportive tools and processes.

Doing adaptive management at Sida - Tim Ruffer; Helen Bailey; Stefan Dahlgren; Patrick Spaven; Mark Winters (Evaluation Brief, 2019)
Lessons from the market systems development approach The evaluation focuses on Sida’s management of MSD projects. The projects are applying the MSD approach with an aim to: - contribute to improved MSD programming by Sida through better management practices across the project cycle - generate recommendations on how Sida can create conducive conditions for systems approaches and adaptive programming more generally. The brief assesses Sida’s organisational capacity for adaptive management in three dimensions: - leadership and culture - staff capacities - skills, and systems and procedures

The Science in Adaptive Management - Ripley, Matt; Jaccard, Sabine (ILO, 2016)
‘Adaptive management’ is all the rage in international development circles. But to avoid yet another buzzword – we need to learn from the experience of natural resource science.
Keywords: IMPORTANT

The Case for an Adaptive Approach to Empowerment and Accountability Programming in Fragile Settings: Synthesis report - Christie, Angela; Green, Duncan (Action for Empowerment and Accountability Research Programme, 2019)
Fragile, conflict and violence-affected settings (FCVAS) are messy and ambiguous contexts in which to plan and implement development initiatives. To work there, external actors are increasingly adopting an adaptive approach to empowerment and accountability (E&A) programming, whatever the setting. This means using a compass rather than map, where real-time political economy analysis (PEA) in relation to context and programme monitoring and evidence-informed learning in relation to intervention are used in combination and in shorter-than-usual planning cycles to maintain and adapt strategic direction. This paper brings together three case studies of large Department for International Development (DFID) governance projects in Myanmar, Nigeria and Tanzania.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Connect. Learn. Adapt. Repeat - Practicing adaptive management in complex, conflict-affected environments: barriers and promising practices - Queen, Emily Forsyth (2018)
To shift aid culture toward adaptive management, we can: - Stay humble, empathetic, and build skills in facilitation and listening. - Focus on working with more flexible foundations or individual donors. Or, work for more rigid donors and help make their policies more flexible. - Get clearer about goals and processes while finding ways to be less specific and more committed to local leadership about pathways to get to the goal. - Resist looking for a magic adaptive management tool and instead get clearer about when teams make what kinds of decisions and matching to tools that support that decision-making. - Validate that everyone’s perspective is a form of data and try out simple ways to document how teams learns and changes. - Broaden and ground the idea of expertise – remembering that, especially when working with folx on the margins, people are the only experts on their own life. Practitioners must also examine how dominant patriarchal, white supremacist, colonial ideas have pushed us toward wanting more control, less flexibility, and less space for equitable decision making.

Adaptive Management looks like it’s here to stay. Here’s why that matters. - Green, Duncan (From Poverty to Power, 2016)
First installment of reflections on my US trip. This is on the rise of adaptive management approaches in USAID, and some of the questions it raises
Keywords: IMPORTANT

Learning to Adapt: Building Adaptive Management as a Core Competency in Development Practice - Ramalingam, Ben (Institute of Development Studies, 2016)
Key messages 1. Development policies and programs increasingly operate in situations of high complexity and uncertainty. 2. There are growing efforts across the sector to design, plan and implement more adaptive responses that are more relevant and appropriate in such contexts 3. At the heart of effective adaptive programming is the capability to gather, interpret and use knowledge, information and data in real-time 4. Strengthening this capability requires a positive enabling environment—including tools and methods, structures and processes, leadership and management and culture and mindsets. 5. For adaptive development to succeed, there needs to be greater attention and investment in both knowledge, information and data systems and in appropriate enabling environments
Keywords: IMPORTANT

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of Institutions for Inclusive Development, Tanzania - Green, Duncan; Guijt, Irene (Action for Empowerment and Accountability Research Programme, 2019)
Adaptive Management involves a dynamic interaction between three elements: delivery, programming and governance. This case study focuses on a large DfID governance project, the Institutions for Inclusive Development (I4ID), a five-year initiative in Tanzania. The study forms part of a research project to examine whether and how adaptive approaches can strengthen aid projects promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). The research examines some of the assertions around the adaptive management approach and explores if and how adaptive approaches, including rapid learning and planning responses (fast feedback loops and agile programming) are particularly relevant and useful for citizen empowerment and government accountability (E&A) in FCVAS.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Agile Development in the Age of Adaptive Management - Davis, Taryn; Orton-Vipond, Sarah; Staid, Martha (Development Gateway, 2019)
Adaptive management – the idea that development projects should respond to real life complexities and be flexible enough to respond to unforeseen changes – is an often-praised approach to doing development differently, with donors and partners exploring how to apply it within their programming.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume I: Evaluation Report - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

Evaluation of the market systems development approach: Lessons for expanded use and adaptive management at Sida Volume II: Case studies - Ruffer, Tim; Bailey, Helen; Dahlgren, Stefan; Spaven, Patrick; Winters, Mark (Evaluation of the market systems development approach, 2018)
This report presents the findings of an evaluation of Sida’s management of the market systems development (MSD) approach. It aims to inform thinking on how Sida can best manage its growing portfolio of MSD programs. Beyond this, it provides insights relevant to Sida’s wider support to complex and adaptive programs. The evaluation identified several factors that affect Sida’s ability to ensure that conducive conditions are in place for effective MSD programs and good development programming more generally. Sida’s relatively flexible framework of rules, guidelines and systems for project management provide the space needed for staff to innovate and manage adaptively. But for this to happen consistently and effectively, Sida needs to invest more deliberately in building the capacity of its staff in relevant areas. In addition, leadership and incentives are key to shaping a culture of active experimentation and learning. This needs to be supported with clearer guidance for those involved in the design and appraisal of MSD projects; and strengthened oversight of project performance, including through adjustments to Sida’s contracts and funding agreements.

ADAPT: Analysis Driven Agile Programming Techniques - IRC (International Rescue Committee (IRC), 2016)
A growing body of research indicates that aid agencies are most successful when able to operate flexibly, particularly in fragile environments. Yet our systems and tools are often too rigid to effectively address complex problems, and program incentives frequently undermine adaptation instead of supporting it. To drive improvements in impact we need to be better able to analyse the dynamics of a given situation, anticipate how these might evolve, and be sufficiently agile to adapt to changes in context and need.

Adaptive Programming in Fragile, Conflict and Violence-Affected Settings, What Works and Under What Conditions?: The Case of PERL, Nigeria - Punton, Melanie; Burge, Richard (Action for Empowerment and Accountability Research Programme, 2018)
This paper examines adaptive approaches to aid programming in Nigeria. Through field research and desk reviews, we have investigated some of the assertions around the ‘adaptive management and programming’ approach, which has arisen in recent years as a response to critiques of overly rigid, pre-designed, blueprint and linear project plans. This is the second of three case studies in a series which explore if and how adaptive approaches, including rapid learning and planning responses, are particularly relevant and useful for promoting empowerment and accountability in fragile, conflict and violence-affected settings (FCVAS). This case study focuses on PERL (Partnership to Engage, Reform and Learn) in Nigeria, a five-year governance programme (2016-21) with a total budget of £100 million. It aims to promote better service delivery through bringing together government and citizens groups to collectively address governance challenges. PERL is viewed by DFID as the final stage of a 20-year investment, building on learning, experience and partnerships from 15 years of DFID-funded governance programming in Nigeria. It was designed to incorporate learning and adaptation through a ‘living’ theory of change, continuous political economy analysis at different levels, adaptive implementation by location-based delivery teams who are encouraged to be flexible and let partners take the lead, regular learning and reflection, and adaptive resourcing, HR and administrative systems. The case study draws on a conceptual framework (the ‘adaptive triangle’) that looks at three types of adaptation – adaptive management, adaptive programming and adaptive delivery – and the interconnections and tensions between them.
Keywords: A4EA; Adaptive Development; Economy; Fishery

Adaptive Action: Leveraging Uncertainty in Your Organization - Eoyang, Glenda H.; Holladay, Royce J. (Stanford University Press, 2013)
Rooted in the study of chaos and complexity, Adaptive Action introduces a simple, common sense process that will guide you and your organization into reflective action. This elegant method prompts readers to engage with three deceptively simple questions: What? So what? Now what? The first leads to careful observation. The second invites you to thoughtfully consider options and implications. The third ignites effective action. Together, these questions and the tools that support them produce a dynamic and creative dance with uncertainty. The road-tested steps of adaptive action can be used to devise solutions and improve performance across multiple challenges, and they have proven to be scalable from individuals to work groups, from organizations to communities. In addition to laying out the adaptive action framework and clear protocols to support it, Glenda H. Eoyang and Royce J. Holladay introduce best practices from exemplary professionals who have used adaptive action to meet personal, professional, and political challenges in leadership, consulting, Alzheimer's treatment, evaluation, education reform, political advocacy, and cultural engagement―readying readers to employ this new toolkit to meet their own goals with a sense of ingenuity and flexibility.

Adaptive development: great progress and some niggles - Vowles, Pete (Medium, 2016)
After 3 years in DFID headquarters, championing adaptive approaches to the delivery of aid and development programmes, I am back in an…

Adaptive Programming: The “Space of Possibility” - Seavey, Sara Mizuta (USAID Learning Lab, 2016)
Sara Mizuta Seavey, M.A., is a Senior Program Officer at FHI360 for the Mobile Solutions Technical Assistance and Research (mSTAR) project, where she works with USAID’s Digital Development Team to conceive, design, and test how real-time data systems can enable a more adaptive and participatory approach to development. She is passionate about systems thinking and participatory approaches to international development. What does space travel have to do with international development?

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.

Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya - Prieto Martin, Pedro; Hernandez, Kevin; Faith, Becky; Ramalingam, Ben (MAVC Research Report, 2017)
Development projects don’t always work as planned. This has long been acknowledged by those in the sector, and has led to several approaches that seek to solve complex development problems through enabling and encouraging greater adaptiveness and learning within projects (e.g. Doing Development Differently and Problem-Driven Iterative Adaptation). Digital development projects experience many of these issues. Using technology for transparency and accountability (Tech4T&A) projects in Kenya as case studies, our research analysed the many different theoretical approaches to learning and adaptation, and then tested how these play out in reality. Firstly, we conducted an extensive review of the literature on the spectrum of approaches to adaptive learning. The findings were used to develop a framework through which to analyse adaptiveness at the different layers of complexity in projects (e.g. software design and development, programme design and management). The second part of the research consisted of interviews and focus group discussions with participants in Tech4T&A projects in Kenya. Respondents helped us identify the main characteristics of adaptiveness in their projects (e.g. who needs to adapt, and how and when) and the challenges and issues that inhibit projects’ abilities to be adaptive. This process also revealed how accountability interplays with adaptiveness, and considered how better collaboration flows can enable adaptiveness. From our literature review and empirical study, we draw several conclusions for increasing adaptiveness in digital development projects. These include simplifying the many adaptive theories that abound, increasing responsiveness to project beneficiaries and stakeholders, and for stakeholders to keep on experimenting, networking and advocating.
Keywords: IMPORTANT

Program Cycle - Discussion Note: Adaptive Management - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

What is adaptive management? - Wilson, Gregory (ΔNTYLLES, 2016)
Recently there has been growing recognition that most development challenges are in actual fact ‘wicked’ problem that requires development actors to recognize that the optimal management approaches…

Implementing Adaptive Approaches in Real World Scenarios: A Nigeria Case Study, with Lessons for Theory and Practice - Bridges, Kate; Woolcock, Michael (The World Bank, 2019)
How does adaptive implementation work in practice? Drawing on extensive interviews and observations, this paper contrasts the ways in which an adaptive component of a major health care project was implemented in three program and three matched comparison states in Nigeria. The paper examines the bases on which claims and counterclaims about the effectiveness of these approaches were made by different actors, concluding that resolution requires any such claims to be grounded in a fit-for-purpose theory of change and evaluation strategy. The principles of adaptive development may be gaining broad acceptance, but a complex array of skills, expectations, political support, empirical measures, and administrative structures needs to be deftly integrated if demonstrably positive operational results are to be obtained, especially when undertaken within institutional systems, administrative logics, and political imperatives that are predisposed to serve rather different purposes.

SAVI Approach Paper 12: Managing Programme Finances to Support Adaptive, Locally-led Processes of Citizen Engagement in Governance - SAVI (DFID, 2016)
SAVI, is seeking to support processes of citizen engagement in governance in ways that are effective in influencing reform, and that are able to take on a life of their own without continuing donor support. SAVI is also an adaptive programme, putting learning and adaptation at the centre of all decision-making. Money is used and...

Top Tips: How to design and manage adaptive programmes - Valters, Craig; Wild, Leni (Overseas Development Institute, 2019)
Within DFID, there is now a commitment to more flexible and adaptive programming. This recognises that: • DFID works in contexts that continuously evolve and change, sometimes in unpredictable ways. To respond to this, the agency needs to remain flexible – to expect change and have a good understanding of context, with resources that can be adjusted and scope to change direction if needed. All DFID programmes should be able to do this. • Some DFID programmes aim to support change in complex systems, behaviours and incentives. Efforts to address women’s empowerment, improve sanitation or build more sustainable health systems, for instance, all require engagement with the way in which complex systems operate and the people and behaviours within them. Trying to deliver reforms in these circumstances is challenging because the pathway to reform itself will be unclear: as a reform is rolled out, the system itself will react and respond. These types of programmes therefore need to build in from the start deliberate processes of learning and testing, to allow for adaptations as more information is gathered for what works over time. These top tips are concerned with programmes that aim to be flexible and adaptive – which work in dynamic contexts and are trying to address complex problems. While there is growing commitment to these approaches, feedback suggests staff still have questions about how to do this well. This document highlights some of the commonly reported issues related to adaptive programming and a set of tips, strategies and examples to help in addressing them. It is aimed at programme managers and advisors who may be Senior Responsible Owners (SROs) or those managing and supporting adaptive programming in a range of ways. We have collated these lessons from discussions with country offices and SROs, feedback from surveys and the wider evidence. We have looked specifically at the adaptive programmes we can find in the DFID portfolio, but this is not an exhaustive list. It should be noted that there is as yet no wide variety of case law to review, but there is a growing set of examples within DFID that can provide continuous learning for the organisation.

Program Cycle - Discussion Note: Managing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Learning and adapting: the use of monitoring and evaluation in countering violent extremism: a handbook for practitioners - Dawson, Laura; Edwards, Charlie; Jeffray, Calum; Royal United Services Institute for Defence and Security Studies (Royal United Services Institute for Defence and Security Studies, 2014)
IN 2013, the Royal United Services Institute for Defence and Security Studies (RUSI) was awarded a grant under the Kanishka Project to develop a handbook for monitoring and evaluating counter violent extremism (CVE) policies and programmes. The aim of this handbook is to support CVE policy-makers and practitioners (those who design, manage and evaluate CVE programmes), by providing them with key terms regarding violent extremism and radicalisation, describing the purpose of evaluation, and providing examples of key methodologies they can employ to conduct monitoring and evaluation (M&E) in this emerging policy field. The handbook will enable readers to understand why, when and how to conduct an evaluation of a CVE policy, programme or project. .

Monitoring and learning for country-level portfolio decision-making and adaptation - Buffardi, Anne L; Mason, Paige; Hutchings, Claire; Sharp, Samuel (Briefing Note, 2019)
Most measurement and adaptive management approaches were developed for and from individual projects. This briefing aims to guide measurement and management of country-level portfolios of work. It identifies potential purposes portfolio-level analyses can fulfil, types of adaptation, and the relative role of monitoring, learning and evaluation (MEL). Drawing on reviews of practice from the United States Agency for International Development (USAID) and the United Kingdom Department for International Development (DFID), guidance notes, and experiences of members of the Global Learning for Adaptive Management (GLAM) initiative, it offers recommendations and considerations that are particularly relevant for this level of analysis and management. Key messages - Portfolio-level analyses can serve eight potential purposes, each of which answers different questions, involves adaptation at different times and levels, and requires different types of evidence. Identifying the purpose(s) and how the component parts relate to each other should guide the development of monitoring and learning systems. - Portfolios are oriented more towards breadth than depth, involve more people with different perspectives, and draw on multiple sources of evidence with potentially greater variation in quality. - In practice, four activities appear to be applied most frequently at a portfolio level: alignment of indicators and aggregation of monitoring data; synthesis of multiple sources and types of information to provide a summary of outputs, outcomes, common observations and trends; periodic review and reflection sessions; and strategic planning, design or refresh of the portfolio strategy. - The extent to which evidence-informed portfolio management is facilitating learning and adaptation has not been well documented to date, and we suggest potential indicators to do so.

Monitoring and Result Measurement for Adaptive Programming - How to Use Data to Manage a MSD Program: Lessons from PRISMA - Khan, Khaled; Seely, Kevin; Ridwan, Mustika; Mulya, Bodhiya (PRISMA, 2019)
Using monitoring data to improve interventions is harder than it seems. Decision-makers are often busy implementing activities, unclear about their roles in data collection and analysis, and uncertain what data matters most or when. PRISMA, an AUD77 million agricultural Market Systems Development (MSD) programme funded by DFAT Australia, has encountered these challenges. With the programme completing its first five year phase, this case study shares ten key lessons divided into three sections: shaping the culture, developing systems, and top management decisions. These lessons aim to help program, sector and intervention managers make better use of monitoring data to improve interventions.

Built to improve: Leveraging realtime M&E for adaptive youth employment programming - Skelton, John (Prospects practice paper, 2, 2016)
Recognising that aid and development programming takes place in complex contexts, Mercy Corps is increasingly seeking to understand how best to manage programs which iterate, adapt and respond to the consistently evolving settings in which we work. This brief Practice Paper provides some examples of what adaptive management looks like in practice on the Prospects youth employment program in Liberia. It does not seek to function as a manual or set of guidelines, but simply provides some practical examples and insights into how a youth employment program governed by principles of adaptive management operates.

Adaptiveness through ‘simplest tools and practices’ - Prieto Martin, Pedro (Institute of Development Studies, 2017)
In recent years, more and more influential development organisations have been openly recognising the central role that adaptive management capacities – the ability to keep improving strategies and actions as programmes unfold – play for the success of complex interventions. As a result, there has been a rich exchange of ideas and experiences on how to promote adaptiveness in development. But development organisations and professionals are having a hard time translating the many adaptive theories and recommendations into improved practices and outcomes. They are generally failing to adjust the design and operation of programmes to accommodate incipient lessons learnt and the unexpected changes in the context. Nowadays, most programme adaptations still take the form of a change of direction once it is clear that things have gone really wrong. Why is so difficult to put what we know about adaptiveness into practice? And more importantly: what can be done to improve this situation?

Help! I’m hiring new staff and I want them to work adaptively. A guide to hiring adaptive employees. - Salib, Monalisa (USAID LEARN, 2019)
If you are involved in hiring, this tool can help you increase your chances of selecting staff members skilled in adaptive management. It will help answer the questions: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? Which interview questions should I ask to screen for adaptive employee competencies? You should use this tool when you decide to hire a new individual - whether that be a direct hire, contractor, or consultant - or when you are changing an individual’s current position description or scope of work. Specifically, this tool will help you determine which qualifications are most important for the position and offers interview questions you can use with candidates. --- You’re in luck! We just released a new guide for hiring adaptive employees. This visual and user-friendly tool will help increase your chances of selecting staff skilled in adaptive management. Here are the details: What do you mean by “work adaptively” or an “adaptive employee”? An adaptive employee is an individual who, in collaboration with relevant stakeholders, systematically acquires and uses knowledge to make decisions and adjustments in their work in order to achieve greater impact. Why focus on adaptive employees? Why does it matter? With industries, technologies, and organizations in a near constant state of flux, leaders are recognizing the importance of adaptability as a critical capacity. Because of this, it’s not surprising that a recent LinkedIn report found that adaptability was the most important soft skill hiring managers were screening for. In addition, evidence shows that teams that apply more data-driven and adaptive leadership practices perform better than those that focus less on these practices. It makes sense, then, that managers want to recruit more team members who are skilled in adaptive management - it helps achieve results. Who should use this tool? Anyone involved in hiring, responsible for developing or approving position descriptions, participating in interviews, and/or approving new hires. When should I use this tool? Use it as soon as you decide to hire a new staff person or when you’re adjusting existing position descriptions. What does the tool help me do? It will help you think through: Which competencies should I recruit for in order to hire more adaptive employees? Which desired qualifications should I incorporate into position descriptions to attract adaptive employees? (You can even copy and paste qualification language from the tool into scopes of work!) Which interview questions should I ask to screen for adaptive employee competencies? (You can copy and paste interview questions into your screening, interview, and reference check protocols!) Has the tool been tested? Yes, staff within USAID’s Global Development Lab and on the USAID LEARN contract tested the tool, providing feedback on the minimum viable product and subsequent versions. Testers confirmed finding the tool useful, and gave it a 9/10 score when asked if they would recommend it to colleagues. Some specific feedback from testers included: "The tool prompts deeper thought on what you might need and want in a job candidate" and "All [of the interview questions I used from the tool] worked well." What about the existing staff? How can they gain greater skills in adaptive management? Existing USAID staff and implementing partners can access online training in collaborating, learning, and adapting (CLA) and find resources in the CLA Toolkit. USAID staff also have access to an internal CLA community of practice and five-day, in-person CLA training.

Doing Development Differently at Scale - Pellini, Arnaldo; Karetji, Petrarca C.; Soekadis, Ade (Knowledge, Politics and Policymaking in Indonesia, 2018)
In recent decades there has been an increasing recognition that politics and political institutions matter for development. There is also a much greater interest in contextually grounded approaches. This has stemmed from an acknowledgement that purely technocratic approaches to development often result in failure because they do not take into account the nature of political institutions. Nor do they take account of the context in a particular developing country and the interests and incentives of powerful national actors. Policy processes are embedded in specific social, political and organisational contexts. Approaches that focus on implementing universal best practices in evidence-informed policymaking are unlikely to be successful. Instead, what is needed is an approach that takes the local context as the starting point for understanding what issues are relevant to policymakers and developing contextually appropriate solutions. The authors of this chapter reflect on the management approaches and systems that may be required to enable and support large-scale development programmes to be flexible and adaptive to the local policy context and circumstances. The chapter argues that such programmes struggle to adopt adaptive management principle and that to do that at scale requires some changes in the way such programmes are managed.
Keywords: Adaptive Management; Doing development differently; Evidence-informed policymaking; Indonesia; Knowledge sector; Thinking and working politically

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2016.08) - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

All about behaviour: KAPE, Adaptation and ' Sticky' Institutional Change - Power, Greg (Politically Agile Programming, 2016)
This paper describes Global Partners Governance’s (GPG’s) approach to institutional reform and political change. Developed over the last decade of working in some of the most complex and sensitive political environments with politicians and officials in parliaments, political parties, ministries and local government, it describes the KAPE® (knowledge-application-practice-effect) methodology that we adopt to get ‘sticky’ institutional and behavioural change. Contents 1) Two dimensions of ‘adaptive programmes’: Flexible delivery and getting behaviour change 2) Enabling Change: KAPE and The Logic of Institutional Reform (Knowledge-Application-Practice-Effect) - K: Knowledge – Defining the problem and what to do about it - A: Application – Making Systems Work in Practice - P: Practice – Pockets of good practice and establishing ‘the new normal’ - E: Effect – Improved performance and the ‘Ripple Effect’ 3) Measuring Impact: Monitoring and Evolving 4) Conclusion: Behavioural insights, adaptive management and sticky change

Learning and adaptation: 6 pitfalls to avoid - Valters, Craig (Devex, 2016)

Try, learn, adapt, repeat: T/A Learn reflections - Alan (www.globalintegrity.org, 2015)
By Alan Hudson — November 16, 2015. I spent last week in Rio de Janeiro (tough assignment, I know), participating in the Transparency and Accountability Initiative’s third T/A Learn Annual Workshop. As the report of the second Annual Workshop, held...

Adaptive Leadership: Accelerating Enterprise Agility - Highsmith, Jim (Addison-Wesley Professional., 2013)

Adapting development: improving services to the poor - Wild, Leni; Booth, David; Cummings, Clare; Foresti, Marta; Wales, Joseph (ODI, 2015)
On current trends, it will take decades or longer to bring basic services to the world’s most disadvantaged people. Meeting this challenge means recognising the political conditions that enable or obstruct development progress - a radical departure from the approach of the Millennium Development Goals.
Keywords: Practice

Complexity, Adaptation, and Results - Barder, Owen; Ramalingam, Ben (Center For Global Development, 2012)
In the last of a series of three blog posts looking at the implications of complexity theory for development, Owen Barder and Ben Ramalingam look at the implications of complexity for the trend towards results-based management in development cooperation. They argue that is a common mistake to see a contradiction between recognising complexity and focusing on results: on the contrary, complexity provides a powerful reason for pursuing the results agenda, but it has to be done in ways which reflect the context. In the 2012 Kapuscinski lecture Owen argued that economic and political systems can best be thought of as complex adaptive systems, and that development should be understood as an emergent property of those systems. As explained in detail in Ben’s forthcoming book, these interactive systems are made up of adaptive actors, whose actions are a self-organised search for fitness on a shifting landscape. Systems like this undergo change in dynamic, non-linear ways; characterised by explosive surprises and tipping points as well as periods of relative stability. If development arises from the interactions of a dynamic and unpredictable system, you might draw the conclusion that it makes no sense to try to assess or measure the results of particular development interventions. That would be the wrong conclusion to reach. While the complexity of development implies a different way of thinking about evaluation, accountability and results, it also means that the ‘results agenda’ is more important than ever.
Keywords: IMPORTANT

Adaptive Management in the Courts - Fischman, Robert L.; Ruhl, J.B. (Minnesota Law Review, 2010)
Adaptive management has become the tonic of natural resources policy. With its core idea of “learning while doing,” adaptive management has infused the natural resources policy world to the point of ubiquity, surfacing in everything from mundane agency permits to grand presidential proclamations. Indeed, it is no exaggeration to suggest that these days adaptive management is natural resources policy. But is it working? Does appending “adaptive” in front of “management” somehow make natural resources policy, which has always been about balancing competing claims to nature’s bounty, something more and better? Many legal and policy scholars have asked that question, with mixed reviews. Their evaluations, however, have rested on theory, program-specific surveys, and isolated case studies. This article provides the first comprehensive review of adaptive management from the perspective that likely matters most to the natural resource agencies practicing adaptive management - how is it faring in the courts? Part I of the Article examines the theory, policy, and practice of adaptive management, focusing on the experience of the federal resource management agencies. The end product in practice is something we call “a m-lite,” a watered down version of the theory that resembles ad hoc contingency planning more than it does planned “learning while doing.” This gap between theory and practice leads to profound disparities between how agencies justify decisions and how adaptive management in practice arrives at the courthouse doorsteps. In Part II we review how these disparities have played out in courts considering claims that agency practice of adaptive management has not lived up to its theoretical promise or to the legal demands of substantive and procedural environmental law. We extract three key themes from the body of case law in this respect. Part III extends from the existing case law to draw lessons for agencies and Congress about the future practice of adaptive management. Our ultimate message to agencies is that a m-lite can be an effective decision method - and one that survives judicial scrutiny - but agencies must be more disciplined about its design and implementation. This includes resisting the temptation to employ adaptive management to dodge burdensome procedural requirements, substantive management criteria, and contentious stakeholder participation. If faithfully followed and enforced, this model, despite its flaws, could serve as an important component of natural resources policy to confront problems of the future as daunting as climate change.

Adaptive Management - Jenal, Marcus; Cunningham, Shawn (Annual Reflection 2019, 2019)

Delivering institutional reform at scale: Problem-driven approaches supported by adaptive programming - Manuel, Clare (Synthesis Paper, 2, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). Second synthesis paper - Delivering institutional reform at scale: problem-driven approaches supported by adaptive programming February 2016 Drawing on our experience on the ground, this peer-reviewed paper suggests how problem driven approaches, supported by adaptive programme management can be implemented at scale in relation to donor programming aimed at institutional reform and improving state capability.
Keywords: IMPORTANT

Adaptive management: why we find it so hard to operationalise - Teskey, Graham (Abt Associates - Governance Soapbox, 2018)

Summer school on Adaptive Management - 2019 - CID (2019)
General description of the curriculum

Making Good Use of Adaptive Management - Doremus, Holly; Andreen, William L.; Camacho, Alejandro E.; Farber, Daniel A.; Glicksman, Robert L.; Goble, Dale D.; Karkkainen, Bradley C.; Rohlf, Dan; Tarlock, A. Dan; Zellmer, Sandra B.; Jones, Shana Campbell; Huang, Yee (White Paper #1104, 2011)

Bridging Real-Time Data and Adaptive Management in International Devepment - Case Study Report - Ramalingam, Ben; Barnett, Inka; Valters, Craig; Oppenheimer, Carrie; Levy, Anna; Hernandez, Kevin (IDS, 2017)

Building a global learning alliance on adaptive management - Wild, Leni; Ramalingam, Ben (ODI, 2018)

Adaptive management: an overview of the concept and its practical application in the Scottish context - Blackstock, Kirsty; Brown, Katrina; Gimona, Alessandro; Prager, Katrin; Irvine, Justin (The James Hutton Institute, 2016)

Adaptive Management: Responding to the evolving needs of PRIME's complex systems - Picon, Diana; Wild, Lorenz (Mercy Corps, 2015)

The road to adaptive management: knowledge, leadership, culture and rules - Byrne, Karri Goeldner; Sparkman, Timothy; Fowler, Ben (The BEAM Exchange, 2016)
Keywords: IMPORTANT; Practice

Developing an effective adaptive monitoring network to support integrated coastal management in a multiuser nature reserve - Vugteveen, Pim; van Katwijk, Marieke M.; Rouwette, Etiënne; Lenders, H. J. Rob; Hanssen, Lucien (Ecology and Society, 2015)
ABSTRACT. We elaborate the necessary conceptual and strategic elements for developing an effective adaptive monitoring network to support Integrated Coastal Management (ICM) in a multiuser nature reserve in the Dutch Wadden Sea Region. We discuss quality criteria and enabling actions essential to accomplish and sustain monitoring excellence to support ICM. The Wadden Sea Long-Term Ecosystem Research project (WaLTER) was initiated to develop an adaptive monitoring network and online data portal to better understand and support ICM in the Dutch Wadden Sea Region. Our comprehensive approach integrates ecological and socioeconomic data and links research-driven and policy-driven monitoring for system analysis using indicators of pressures, state, benefits, and responses. The approach and concepts we elaborated are transferable to other coastal regions to accomplish ICM in complex social-ecological systems in which scientists, multisectoral stakeholders, resource managers, and governmental representatives seek to balance long-term ecological, economic, and social objectives within natural limits.
Keywords: IMPORTANT

Short Course - Adaptive Management, an overview - Bazaz Smith, Komal (American University, 2019)

Summer School Course - Adaptive Management - Working Effectively in the Complexity of International Development (weekplan) - Green, Duncan; Guijt, Irene (Oxfam, 2018)

Adaptive management: What it means for CSOs - O’Donnell, Michael (Bond, 2016)
Keywords: IMPORTANT

How to set up and manage an adaptive programme - Lessons from the Action on Climate Today (ACT) Programme - Cooke, Katherine (OPM, 2017)

DFID’s approach to value for money in programme and portfolio management - ICAI (Independent Commission for Aid Impact (ICAI), 2018)
ICAI published this review on DFID’s approach to value for money in February 2018, and as value for money is both a process and an outcome and cuts across all aspects of DFID’s operations, did not score this review. We made five recommendations and published a follow-up to this review in July 2019. All UK government departments are required to achieve value for money in their use of public funds. In recent years, DFID has been working to build value for money considerations further into its management processes and its relationships with implementers and multilateral partners, establishing itself as a global champion on value for money. Review This review was published in February. Though it was not rated, ICAI made five recommendations, and found that the Department for International Development’s approach to value for money was helping to make UK aid spending go further, but improvements are still needed. Findings This review found that DFID has strengthened its processes and systems for ensuring it gains maximum value for each pound spent, has taken swift remedial action to tackle under-performing programmes, and has become a strong global champion on value for money. The review also found that DFID has been diligent in its efforts to cut waste, detect fraud, and improve efficiency, and that this work is improving the return on the UK investment in aid. However, the review found that DFID’s approach was not adequately reporting and capturing results and value for money at the country portfolio level, or how programmes work together to deliver lasting impact, including reducing future dependency on aid. It also found that weakness in the annual review process could undermine DFID’s approach to value for money. It found that targets were frequently revised, and that there could be pressures for optimistic scoring of programmes. Recommendations Based on this review, we made the following five recommendations to help DFID improve its approach to value for money still further: DFID country offices should articulate cross-cutting value for money objectives at the country portfolio level, and should report periodically on progress at that level. Drawing on its experience with introducing adaptive programming, DFID should encourage programmes to experiment with different ways of delivering results more cost-effectively, particularly for more complex programming. DFID should ensure that principles of development effectiveness – such as ensuring partner country leadership, building national capacity and empowering beneficiaries – are more explicit in its value for money approach. Programmes should reflect these principles in their value for money frameworks, and where appropriate incorporate qualitative indicators of progress at that level. DFID should be more explicit about the assumptions underlying the economic case in its business cases, and ensure that these are taken into account in programme monitoring. Delivery plans should specify points in the programme cycle when the economic case should be fully reassessed. Senior responsible owners should also determine whether a reassessment is needed following material changes in the programme, results targets or context. Annual review scores should include an assessment of whether programmes are likely to achieve their intended outcomes in a cost-effective way. DFID should consider introducing further quality assurance into the setting and adjustment of logframe targets.

SAVI Approach Paper 14: Learning, Adaptation and Communications - SAVI (DFID, 2016)
SAVI, a DFID funded programme implemented by Palladium, is an adaptive programme, aiming to put learning and adaptation at the centre of all decision-making. Learning and adaptation takes place in SAVI at three levels: the work of partners; the work of SAVI delivery teams; and the enabling environment of the programme as a whole. Achieving...

Evidence Base for Collaborating, Learning, and Adapting: summary of the literature review (2017 update) - Learning Lab (USAID, 2017)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Thoughts on the use of hypotheses in adaptive management - Sparkman, Timothy (BEAM Exchange, 2015)
New insights, opinions and perspectives on market systems development, from experts and practitioners.

Policy experimentation and innovation as a response to complexity in China’s management of health reforms - Husain, Lewis (Globalization and Health, 2017)
There are increasing criticisms of dominant models for scaling up health systems in developing countries and a recognition that approaches are needed that better take into account the complexity of health interventions. Since Reform and Opening in the late 1970s, Chinese government has managed complex, rapid and intersecting reforms across many policy areas. As with reforms in other policy areas, reform of the health system has been through a process of trial and error. There is increasing understanding of the importance of policy experimentation and innovation in many of China’s reforms; this article argues that these processes have been important in rebuilding China’s health system. While China’s current system still has many problems, progress is being made in developing a functioning system able to ensure broad population access. The article analyses Chinese thinking on policy experimentation and innovation and their use in management of complex reforms. It argues that China’s management of reform allows space for policy tailoring and innovation by sub-national governments under a broad agreement over the ends of reform, and that shared understandings of policy innovation, alongside informational infrastructures for the systemic propagation and codification of useful practices, provide a framework for managing change in complex environments and under conditions of uncertainty in which ‘what works’ is not knowable in advance. The article situates China’s use of experimentation and innovation in management of health system reform in relation to recent literature which applies complex systems thinking to global health, and concludes that there are lessons to be learnt from China’s approaches to managing complexity in development of health systems for the benefit of the poor.

Managing staff transistions through CLA: preserving institutional memory as staff come and go - USAID (CLA Toolkit, 2019)
This document is relevant for any position or hiring mechanism. While this document does not explicitly address what happens when someone arrives into a newly-created position, which has its own set of challenges, many of the principles, actions, and resources can be applied in that context. Section 1 offers guidance for how to set up and implement systems at Mission/OU or office to ensure that all staff help preserve institutional memory and enable continuity of relationships. This section is for any staff in a Mission/OU working to build systems that improve handovers and knowledge capture and sharing across the Mission or OU. If a Mission or OU is just beginning to develop a system to manage staff transitions, you may want to start by developing a system within an office or team and then expand it out to other offices or to the Mission/OU writ large. Section 2 includes key principles and actions individuals could consider following when arriving or departing a position, regardless of hiring mechanism and position. This includes staff new to the Mission/OU and staff who are currently in the Mission/OU and are moving into a new position. Section 3 provides a select number of resources to help you take a systematic and comprehensive approach to manage staff transitions as effectively and efficiently as possible at the individual or organizational level.

Contracts for adaptive programming - Bryan, Kevin; Carter, Paddy (ODI, 2016)
Adaptive programming is an approach to development that encourages experimentation, learning & adaptation. This report examines the contractual underpinnings of this approach.

Six things that help grant-makers learn and adapt - Murray, Aoife (Itad, 2017)
There’s an emerging body of literature identifying key strategies that can both improve learning and enable adaptive management amongst grant-makers. We recently reviewed a host of publications from eight grant-making organisations. Those organisations have diverse aims and approaches but we’ve identified six common themes that stand out: Strong leadership and facilitation enables successful learning and …

edX MOOC: Adaptive Leadership in Development - edX (edX, 2016)
Gain the skills to be an adaptive leader in development and learn how to uncover local solutions to complex problems in developing countries.

Scrambling after Moving Targets: Monitoring & Evaluation Applied to Adaptive Management Approaches in Peacebuilding - Woodrow, Peter; Jean, Isabella (New Directions in Peacebuilding Evaluation, 2019)
In this landmark collection, the voices of pathMakers and innovators in peacebuilding evaluation are assembled to provide new direction for the field.
Keywords: IMPORTANT

Program Cycle - Discussion Note: Designing Monitoring, Evaluation, and Learning Platforms - USAID (USAID, 2018)
This Discussion Note complements ADS 201.3.1.2 Program Cycle Principles by elaborating on Principle 2: Manage Adaptively through Continuous Learning. This Discussion Note is intended for USAID staff interested in learning about recent and promising practices in adaptive management across the Program Cycle.

Towards an Alternative Development Management Paradigm? - Shutt, Cathy (Rapport 2016:07, 2016)
Demonstrating results has been a concern in international development cooperation ever since it was started and in recent years there has been an increased focus on achieving and reporting on “results”. Despite the fact that everyone involved in development cooperation wants to make a difference there has been a growing criticism from practitioners about the “results agenda” based on a concern that the approaches used are not fit for purpose. In the EBA-report, Cathy Shutt, at the University of Sussex, scrutinizes the recent critical debate about results based management, and the main arguments and motives behind the criticism. She shows that the debate is not only a matter of obsessive measurement and reporting of meaningless numbers for political accountability, but also a matter of problematic assumptions and how we think about development, evidence and learning. In the report, Shutt also explores what could be learned from those who are not just critiquing results based management approaches but also proposing alternatives. Are these new alternatives an answer to the criticism?
Keywords: IMPORTANT

Navigation by Judgment: Why and when Top Down Management of Foreign Aid Doesn't Work - Honig, Dan (Oxford University Press, 2018)
Foreign aid organizations collectively spend hundreds of billions of dollars annually, with mixed results. Part of the problem in these endeavors lies in their execution. When should foreign aid organizations empower actors on the front lines of delivery to guide aid interventions, and when should distant headquarters lead? In Navigation by Judgment, Dan Honig argues that high-quality implementation of foreign aid programs often requires contextual information that cannot be seen by those in distant headquarters. Tight controls and a focus on reaching pre-set measurable targets often prevent front-line workers from using skill, local knowledge, and creativity to solve problems in ways that maximize the impact of foreign aid. Drawing on a novel database of over 14,000 discrete development projects across nine aid agencies and eight paired case studies of development projects, Honig concludes that aid agencies will often benefit from giving field agents the authority to use their own judgments to guide aid delivery. This "navigation by judgment" is particularly valuable when environments are unpredictable and when accomplishing an aid program's goals is hard to accurately measure. Highlighting a crucial obstacle for effective global aid, Navigation by Judgment shows that the management of aid projects matters for aid effectiveness.

Using adaptive development to support feminist action - O’Neil, Tam (ODI, 2016)
This paper looks at how adaptive development is being applied by gender programmes and argues that gender and adaptive development communities have much to offer each other.

DRG Center practical tips to implement more context-adaptive programming - Jacobstein, David (#AdaptDev, 2018)
Hi #adaptdevers, The cross-sectoral programs team in the DRG Center have been working in support of ways that programming can be made more aware of, and responsive to, context considerations that have to do with incentives and relationships between different actors - often called power dynamics or political economy. Following several discussions with field folks, we were asked to come up with simple and practical tips that could help staff to implement more context-adaptive programming, or to better Work Politically to use TWP jargon. With assistance from many of our field staff and partners, we've put together three documents (to start) that have now been cleared to share publicly: • Tips on Making Your Solicitations Invite Context-Driven Adaptive Programming - suggestions spanning most sections of a typical solicitation to better weave in Thinking and Working Politically. I'm particularly excited that this document contains embedded links to excerpts from a set of solicitations that model good practice. You can also find a summary of all the excerpts from real solicitations, and links onward to the public posting of those solicitations on Fed Biz Ops or Grants.gov, here. • Tips on Power Dynamics and Theories of Change - suggestions relevant to those working on project designs and logic models. • Tips for Better Use of Advisory Councils - suggestions to set up better advisory bodies that help you to incorporate political economy more automatically into your programmatic adjustments. I hope that you'll find these practical and helpful! Feedback is always welcome. Best, David

Evaluation and learning in complex, rapidly changing health systems: China’s management of health sector reform - Xiao, Yue; Husain, Lewis; Bloom, Gerald (Globalization and Health, 2018)
Healthcare systems are increasingly recognised as complex, in which a range of non-linear and emergent behaviours occur. China’s healthcare system is no exception. The hugeness of China, and the variation in conditions in different jurisdictions present very substantial challenges to reformers, and militate against adopting one-size-fits-all policy solutions. As a consequence, approaches to change management in China have frequently emphasised the importance of sub-national experimentation, innovation, and learning. Multiple mechanisms exist within the government structure to allow and encourage flexible implementation of policies, and tailoring of reforms to context. These limit the risk of large-scale policy failures and play a role in exploring new reform directions and potentially systemically-useful practices. They have helped in managing the huge transition that China has undergone from the 1970s onwards. China has historically made use of a number of mechanisms to encourage learning from innovative and emergent policy practices. Policy evaluation is increasingly becoming a tool used to probe emergent practices and inform iterative policy making/refining. This paper examines the case of a central policy research institute whose mandate includes evaluating reforms and providing feedback to the health ministry. Evaluation approaches being used are evolving as Chinese research agencies become increasingly professionalised, and in response to the increasing complexity of reforms. The paper argues that learning from widespread innovation and experimentation is challenging, but necessary for stewardship of large, and rapidly-changing systems.

Interview protocol: Most significant turning points - Prieto Martin, Pedro; Faith, Becky (Institute of Development Studies, 2017)
This interview protocol was used for a research project on adaptiveness in technology for governance initiatives in Kenya. For more information, please read the research report at: Prieto Martin, P.; Hernandez, K.; Faith, B. and Ramalingam, B. (2017) Doing Digital Development Differently: Lessons in adaptive management from technology for governance initiatives in Kenya, MAVC Research Report, Brighton: Institute of Development Studies, ids.ac.uk/project/making-all-voices-count
Keywords: IMPORTANT

How DFID can better manage complexity in development programming - Sharp, Samuel; Valters, Craig; Whitty, Brendan (ODI, 2019)
The United Kingdom’s (UK) Department for International Development (DFID) is an ambitious government department that is committed to reducing poverty and conflict overseas. Many of the issues on which DFID works are complex; whether focused on climate change, gender equality, health or other priorities, simple solutions rarely exist. And to tackle these complex challenges, DFID staff must interact with unpredictable systems of political, organisational and individual behaviours and incentives. There is a risk that complex problems spur more complicated programmes; that the complexity of development challenges is addressed through designing programmes with too many projects and implementers. While there may be valid reasons for this, too many of these complicated programmes will overburden staff. This briefing note is the outcome of an ongoing process within DFID to confront these issues and answer the question: how can DFID design and manage programmes to address complex development challenges without creating too much staff workload? Key messages DFID deals with complex problems, which require flexible systems to support testing, learning and adaptation. • Complex problems do not necessarily require workload-heavy delivery structures, but simpler approaches depend on delivery partners’ experience and competence. • However, programmes that tackle complex problems do require more hands-on engagement and face more workload from inflexible compliance requirements. We suggest that DFID and similar agencies: • Pay closer attention to delivery options in programme design, making use of existing options where possible and, where not, fostering local organisations through long-term investments. • Encourage programme designers to articulate how ambition matches resources and consider ‘good enough’ design. • Reduce the burden of compliance by cultivating partner autonomy, reassessing results and valuefor-money requirements and promoting more flexible contracting and procurement. • Plan and prioritise management resources across a portfolio of programmes to make sure they can be focused in the right areas, where the complexity of the problem requires greater engagement.

Timely evaluation in international development - Webster, Jayne; Exley, Josephine; Copestake, James; Davies, Rick; Hargreaves, James (Journal of Development Effectiveness, 2018)
Impact and process evaluations are increasingly used in international development; however they are generally retrospective in outlook. A more timely approach to evaluation aims to identify necessary, feasible and effective changes during a programme or intervention’s lifetime. This paper aims to identify, categorise, describe and critically appraise methods to support more timely evaluation in international development. Potential methods were identified through scoping seminar, public symposium, targeted review of the literature, and the authors’ own experiences and opinions. Findings from the different data sources were reviewed collectively by the author group and triangulated to develop an analytical framework. We identified four purposes of timely evaluation for international development, and critiqued the use of approaches against four dimensions of timeliness and flexibility. Whilst we found significant interest in more timely approaches to evaluation in international development, there was a dearth of published empirical evidence upon which to base strong recommendations. There is significant potential for timely evaluation to improve international development outcomes. New approaches to mixing and adapting existing methods, together with new technologies offer increased potential. Research is needed to provide an empirical evidence base upon which to further develop the application, across sectors and contexts, of timely evaluation in international development.
Keywords: Adaptive learning; Outcome evaluation; Programme improvement; impact evaluation

Real-Time Data for Adaptive Management at USAID - Doshi, Samir (Health Communication Innovation Webinar, 2016)

‘Learning journeys’ for adaptive management – Where does it take us? - Ørnemark, Charlotte (GPSA Note 12, 2016)
Keywords: IMPORTANT

Fostering Learning in Large Programmes and Portfolios: Emerging Lessons from Climate Change and Sustainable Development - Harvey, Blane; Pasanen, Tiina; Pollard, Alison; Raybould, Julia (Sustainability, 2017)
In ﬁelds like climate and development, where the challenges being addressed can be described as “wicked”, learning is key to successful programming. Useful practical and theoretical work is being undertaken to better understand the role of reﬂexive learning in bringing together different knowledge to address complex problems like climate change. Through a review of practical cases and learning theories commonly used in the areas of resilience, climate change adaptation and environmental management, this article: (i) reviews the theories that have shaped approaches to reﬂexive learning in large, highly-distributed climate change and resilience-building programmes for development; and (ii) conducts a comparative learning review of key challenges and lessons emerging from early efforts to promote and integrate reﬂexive learning processes in programmes of this nature. Using a case study approach, the authors focus on early efforts made in four large, inter-related (or nested) programmes to establish, integrate and sustain learning processes and systems. Eight themes emerged from the review and are considered from the perspective of learning programmes as emergent communities of practice. By investigating how these themes play out in the nested programming, the paper contributes to the limited existing body of evidence on learning in large climate change programmes and identiﬁes areas where future efforts might focus.

Paradoxes and partnerships: a study of knowledge exploration and exploitation in international development programmes - Lannon, John; Walsh, John N. (Journal of Knowledge Management, 2019)
Purpose – This paper aims to look at how organisational partnerships balance knowledge exploration and exploitation in contexts that are rife with paradoxes. It draws on paradox theory to examine the partnership’s response to the explore-exploit relationship.

Planning & Navigating Social Change - Tools for Pacific voyagers - Orr, Douglas Epeli; Cavatore, Maria; Aston, Tom (Oxfam, 2019)
Those working to advance social change in the Pacific must understand, work with and respond to the complex and changing relationships and dynamics of power that exist within such networks, and situate their work in the context of decolonisation and self-determination. But the approaches typically used by NGOs to plan our projects and programs have failed to give due attention to these dynamics. The result is that our projects fall short of achieving their promise, despite being technically sound and logical. In this guide, we aim to provide a process and tools that prioritise and draw out the rich, often implicit, knowledge that Pacific Islanders have about our contexts to plan and manage social change initiatives in a manner that values and responds to this ocean of relationships. Drawing from these relationship-based and voyaging traditions, we emphasise the need to: • frame change in terms of change in people; e.g. change in the situation of groups of people and change in terms of the actions of people; • identify a course towards a particular ‘change destination’; • identify the signs to read that will help you determine where you are on that course; • be constantly attentive to the context as you make the journey, and • be ready to adjust your course in response to changes in your context. To support this way of working, we have selected a number of tools from approaches that we believe fit. In particular, we have drawn from the following approaches: • Thinking and Working Politically and other ‘politically aware’ approaches that recognise that the success of a development initiative will be determined by the interplay of relationships of power within a particular context, not just by having the right technical solution; • Outcome mapping because of its focus on people and relationships, and on identifying and supporting needed changes in the behaviour of specific actors in relation to others. This is key, because it’s individuals who deliver services, individuals who decide whether to allocate budget and resources to address a problem, and individuals who make the choice to believe whether a service is relevant to solving their issues; • Adaptive management because of its recognition that development initiatives take place within complex and changing systems and need to adjust to these and that this requires ongoing learning and adaptation.

A Guide to Digital Feedback Loops. An approach to strengthening program outcomes through data for decision making - Whittle, Dennis; Campbell, Megan (USAID, 2019)
Feedback is information about what happens as a result of what you do. Using that information to adapt what you do or how you do it creates what is called a feedback loop. A digital feedback loop uses digital technology at some stage of the feedback loop. Digital feedback loops help USAID missions improve the effectiveness and efficiency of their activities and can support partner countries on their journey to self-reliance through increased information sharing and improved government and civil society capacity. USAID missions and their partners have used digital feedback loops to improve HIV treatment targeting in Zimbabwe, engage three million young people in Nigeria in policy, and reduce field reporting times from one month to one day. Digital feedback loops provide access to information faster and more cheaply than ever before. As part of an adaptive management approach, digital feedback loops increase our ability to act on opportunities and respond to challenges. That in turn can improve outcomes and reduce the risk of waste and failure. This guide outlines the case for integrating digital feedback loops into your work, and provides tools, resources and guiding questions to support you as you get started. The guide includes examples of how USAID missions are using digital feedback loops to improve their programs in various sectors and provides worksheets to help you apply digital feedback loops to your own context.

Leading Change Through Adaptive Design - Berstein, Maya; Linsky, Marty (Stanford Social Innovation Review, 2016)
By integrating two practices—design thinking and adaptive leadership—social innovators can manage projects in a way that’s both creatively confident and relentlessly realistic.

Donor perceptions and processes: Risks to success of adaptive programming? - Browse - Knowledge Platform Security & Rule of Law - Donovan, Elbereth (Knowledge Platform - Security & Rule of Law, 2017)
Keywords: IMPORTANT

How can we be more adaptive? AdaptScan identifies critical areas for improvement - Mercy Corps (Mercy Corps & IRC, 2017)
Keywords: IMPORTANT

Adaptive Programming and Business Environment Reform – Lessons for DFID Zimbabwe - Donovan, Elbereth; Manuel, Clare (DFID, 2017)
Keywords: IMPORTANT

From analysis to action: operationalising learning and adaptation in Savings at the Frontier - Salehi, Yusef (2016)
Keywords: IMPORTANT

Learning, monitoring and evaluating: achieving and measuring change in adaptive programmes - Callaghan, Sarah; Plank, Georgia (Synthesis Paper, 5, 2017)

Adaptive programming - Vowles, Pete (DFID Bloggers, 2013)
Staff blogs from the UK Department for International Development. Get real-life perspectives from those on the ground to fight poverty and join in the debate.

Course: Introduction to Collaborating, Learning and Adapting (CLA) in the Program Cycle - USAID LEARN (USAID Learning Lab, 2018)

Re-Perceiving Results: Aid Programs and Change in Fragile Societies - van Veen, Erwin; Rijper, Alies (Policy Brief, 2017)
Aid programmes need to be able to adapt their objectives and operations to changes in their political environment, since development processes are subject to political contestation. Change takes time and is often a matter of seizing the opportunity.
Keywords: IMPORTANT

Politics matters, so what? Time for bigger bets (and more learning) on adaptive programming - Alan (www.globalintegrity.org, 2016)
By Alan Hudson, Executive Director, Global Integrity, July 26, 2016 Politics matters. Context too. And blueprints have limited value. Our strategy is based on these insights, so we’re totally on board. A World Development Report (WDR) that puts power and politics...

Extreme Teaming: Lessons in Complex, Cross-Sector Leadership - Edmondson, Amy C.; Harvey, Jean-Francois (Emerald Publishing, 2017)
Extreme Teaming Lessons in Complex, Cross-Sector Leadership Today’s global enterprises increasingly involve collaborative work by teams of experts operating across different professions, organizations, and industries. Extreme Teaming provides new insights into the world of complex, cross industry projects and the ways they must be managed. Leading experts Amy Edmondson and Jean-François Harvey analyze contemporary cases that expose the complex demands of cross-boundary collaboration on management, and inform our understanding of teams. Containing powerful insights and practical guidelines that allow managers to bridge professional divides and organizational boundaries in order to work together effectively, this is a new exploration of the challenges involved in today’s global enterprises. The authors demonstrate that the work done in the modern organization is less and less about looking inward and creating strong teams inside the company, and more about teaming across boundaries – that often are in flux. Extreme Teaming is a must-read book for all courses related to leading open innovation; teamwork and collaboration; project management; and cross-boundary work.

LEARN Monitoring, Evaluation, Research, and Learning Plan - Learning Lab (USAID, 2016)
LEARN and USAID/PPL are managing an area of work known as Evidence Base for Collaborating, Learning, and Adapting (EB4CLA). The purpose of this work is to answer key learning questions:

Adapting Aid: Lessons from six case studies - Algoso, Dave; Beloe, Jon; Hemberger, Alison; Hill, Philippa; Proud, Emma (MercyCorps & IRC, 2016)
Keywords: IMPORTANT

SAVI Approach Paper 15: Introduction to PERL: the SAVI Successor Programme - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Nigeria Public Sector Accountability and Governance Programme - Business Case - SAVI (DFID, 2016)
In May 2016, SAVI transitioned into a successor programme – the ‘Engaged Citizens Pillar’ (ECP) of a wider DFID-funded governance reform programme ‘The Partnership to Engage, Reform and Learn’ (PERL). ECP is managed by the same service provider, Palladium, and the same core management team as SAVI, and many of the SAVI front line staff...

Exploring ways to reconcile accountability and learning in the evaluation of niche experiments - Regeer, Barbara J.; de Wildt-Liesveld, Renée; van Mierlo, Barbara; Bunders, Joske F. G. (Evaluation, 2016)
While evaluation is seen as a mechanism for both accountability and learning, it is not self-evident that the evaluation of niche experiments focuses on both accountability and learning at the same time. Tensions exist between the accountability-oriented needs of funders and the learning needs of managers of niche experiments. This article explores the differences in needs and expectations of funders and managers in terms of upwards, downwards and internal accountability. The article shows that as the multi-stakeholder contexts in which niche experiments take place give rise to various requirements, tensions in evaluation are essentially a specific manifestation of tensions between niche experiments and their multiple contexts. Based on our findings, an adjusted accountability framework is proposed, including several strategies that can reconcile a learning approach with accountability needs in niche experiments aiming to change current practices in a more sustainable direction.

Building capability by delivering results: Putting Problem-Driven Iterative Adaptation (PDIA) principles into practice - Andrews, Matt; Pritchett, Lant; Samji, Salimah; Woolcock, Michael (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Transformation, politics and implementation: smart implementation in governance programs - Kirsch, Renate; Siehl, Elke; Stockmayer, Albrecht (Nomos, 2017)
Working in environments characterised by a high degree of uncertainty, uncontrollability and unpredictability, development agents try to organise complex realities into manageable units. What principles influence the decision on adequate approaches and necessary steps? Through theoretical considerations and nine case studies, the GIZ traces implementation processes and identifies underlying guiding principles which provide the flexibility and adaptability that is necessary for acting in complex contexts. Main findings show that an adaptive and reflexive management structure is crucial for successful implementation. Quick iteration and tight feedback loops facilitate adaptation and reorientation. Contextsensitive knowledge and constant monitoring create a space for learning and innovation. A joint vision for the future which is used for orientation purposes and can be modified according to new findings and developments fosters fruitful cooperation.

DFID’s approach to delivering impact - ICAI (Independent Commission for Aid Impact (ICAI), 2015)
UK aid, at its best, makes a real and positive difference to the lives and livelihoods of poor people around the world. Ensuring the best possible performance across a large and multifaceted aid programme is, however, a complex management challenge. This report reviews ICAI’s previous 44 reports and looks at how well DFID ensures positive, long-term, transformative impact across its work.

Announcement of CLA Learning Network Launch - Lab, Learning (USAID Learning Lab, 2016)
USAID’s Bureau for Policy, Planning and Learning (PPL), together with the Bureau for Economic Growth, Education, and Environment’s localworks program, is pleased to announce the launch of a Learning Network focused on building the evidence base for Collaborating, Learning and Adapting (CLA).

SAVI Approach Paper 5: Defining and Measuring Results - SAVI (DFID, 2015)
SAVI aims to facilitate replicable and sustainable processes of citizen engagement in governance. The programme in each state is locally defined, flexible and adaptive, and results are not predictable in advance. Standardised monitoring tools are not applicable, and consequently we have evolved our tools and frameworks during the programme through processes of learning by doing....

Essentials of Utilization-Focused Evaluation - Patton, Michael Quinn (SAGE Publications, 2011)
Based on Michael Quinn Patton's best-selling Utilization-Focused Evaluation, this briefer book provides an overall framework and essential checklist steps for designing and conducting evaluations that actually get used. The new material and innovative graphics present the utilization-focused evaluation process as a complex adaptive system, incorporating current understandings about systems thinking and complexity concepts. The book integrates theory and practice, is based on both research and professional experience, and offers new case examples and cartoons with Patton's signature humor.
Keywords: Reference / Research; Research

Lessons for Effective resilience programs: a case study of the RAIN program in Ethiopia - Kleiman, Shanti (Mercy Corps, 2013)
The RAIN program experience affirms the importance of multi-year and flexible funding as key program design features if progress in resilience building is to be supported in areas with high levels of structural and temporal vulnerability. These features enable management to respond effectively to changing circumstances in order to better meet the needs of communities and to create the necessary conditions for relief-to-development strategies to take hold. Finally, this study found that deliberate and effective coordination between donor agencies can ensure that development gains achieved during one program period are directly leveraged by subsequent programs, thereby increasing the effectiveness of resilience programs.

The Rapid Evaluation, Action, and Learning (REAL) Approach: A toolkit to measure and refine changes and interventions in health campaigns - PATH (PATH, 2019)
Evaluative Tools for Improving Campaign Effectiveness Public health campaigns aim to control disease or deliver essential health services and products through time-limited and periodic channels. Many countries use campaigns to augment or replace routine service delivery, to target certain populations, or to accelerate progress towards coverage targets. The Root Cause Analysis and Rapid Evaluation, Action, and Learning toolkits present a systematic but flexible approach to identifying the root causes of campaign bottlenecks and then designing, testing, and refining solutions to optimize potential impact. These toolkits respond to a growing need for “fit-for-purpose” rapid-testing, adaptive learning approaches to evaluation and the need for a culture shift toward iterative adaptation and improvement that integrates measurement and evidence-informed decision-making into daily practice. The comprehensive package of toolkits, in addition to the individual Root Cause Analysis toolkit and Rapid Evaluation, Action, and Learning toolkit are available below.

USAID ADS 201 - Program Cycle Operational Policy (Update 1/23/2017) - USAID (USAID, 2017)
The Program Cycle is USAID’s operational model for planning, delivering, assessing, and adapting development programming in a given region or country to advance U.S. foreign policy. It encompasses guidance and procedures for: 1) Making strategic decisions at the regional or country level about programmatic areas of focus and associated resources; 2) Designing projects and supportive activities to implement strategic plans; and 3) Learning from performance monitoring, evaluations, and other relevant sources of information to make course corrections as needed and inform future programming.

Team of Teams: New Rules of Engagement for a Complex World - McChrystal, General Stanley; Silverman, David; Collins, Tantum; Fussell, Chris (Portfolio Penguin, 2015)
As commander of Joint Special Operations Command (JSOC), General Stanley McChrystal discarded a century of management wisdom and pivoted from a pursuit of mechanical efficiency to organic adaptability. In this book, he shows how any organization can make the same transition to act like a team of teams - where small groups combine the freedom to experiment with a relentless drive to share their experience.Drawing on a wealth of evidence from his military career and sources as diverse as hospital emergency rooms and NASA's space program, McChrystal frames the existential challenge facing today's organizations, and presents a compelling, effective solution.

Teaming: how organizations learn, innovate, and compete in the knowledge economy - Edmondson, Amy C. (Jossey-Bass, 2012)
New breakthrough thinking in organizational learning, leadership, and change Continuous improvement, understanding complex systems, and promoting innovation are all part of the landscape of learning challenges today's companies face. Amy Edmondson shows that organizations thrive, or fail to thrive, based on how well the small groups within those organizations work. In most organizations, the work that produces value for customers is carried out by teams, and increasingly, by flexible team-like entities. The pace of change and the fluidity of most work structures means that it's not really about creating effective teams anymore, but instead about leading effective teaming. Teaming shows that organizations learn when the flexible, fluid collaborations they encompass are able to learn. The problem is teams, and other dynamic groups, don't learn naturally. Edmondson outlines the factors that prevent them from doing so, such as interpersonal fear, irrational beliefs about failure, groupthink, problematic power dynamics, and information hoarding. With Teaming, leaders can shape these factors by encouraging reflection, creating psychological safety, and overcoming defensive interpersonal dynamics that inhibit the sharing of ideas. Further, they can use practical management strategies to help organizations realize the benefits inherent in both success and failure. Presents a clear explanation of practical management concepts for increasing learning capability for business results Introduces a framework that clarifies how learning processes must be altered for different kinds of work Explains how Collaborative Learning works, and gives tips for how to do it well Includes case-study research on Intermountain healthcare, Prudential, GM, Toyota, IDEO, the IRS, and both Cincinnati and Minneapolis Children's Hospitals, among others Based on years of research, this book shows how leaders can make organizational learning happen by building teams that learn.

Moving Targets, Widening Nets: monitoring incremental and adaptive change in an Empowerment and Accountability programme. The experience of the State Accountability and Voice Initiative in Nigeria - Derbyshire, Helen; Barr, Julian; Fraser, Steve; Mwamba, Wilf (DFID, 2016)
Keywords: IMPORTANT; Practice

Inclusive rigour for complexity - Chambers, Robert (Journal of Development Effectiveness, 2015)
Rigour can be reductionist or inclusive. To learn about and understand conditions of complexity, emergence, nonlinearity and unpredictability, the inclusive rigour of mixed methods has been a step in the right direction. From analysis of mixed methods and participatory approaches and methods, this article postulates canons for inclusive rigour for research and evaluation for complexity: eclectic methodological pluralism; improvisation and innovation; adaptive iteration; triangulation; plural perspectives; optimal ignorance and appropriate imprecision; and being open, alert and inquisitive. Inclusive rigour is inherent in participatory methods and approaches, visualisations, group-visual synergy, the democracy of the ground and participatory statistics. Transparent reflexivity, personal behaviour and attitudes, and good facilitation are fundamental. Fully inclusive rigour for complexity demands many personal, institutional and professional revolutions.
Keywords: Evaluation; Mixed methods; Participatory methodologies; Research; paradigm; rigour

Multi-project programmes functions, forms and implications for evaluation and learning - Buffardi, Anne; Hearn, Simon (Methods Lab, 2015)
Multi-project programmes can serve different purposes. For instance, they may coordinate multiple implementing entities; standardise management and technical support; compare intervention approaches across different contexts; enhance leverage through joint action; or foster sustainability by building relationships among organisations. • At the same time, multi-project programmes are costly, potentially duplicate other mechanisms that fulfil similar functions, and can dilute focus and create confusion. • To guide decisions on what coordination, evaluation and learning mechanisms are needed, it is helpful to articulate the intended purpose of using a programme model. Identifying the purpose(s) can help staff determine what types of knowledge sharing strategies may be most useful to the programme, and how project and programme theories of change can be sequenced

When theory meets reality: assumptions, feasibility and implications of a complexity-informed approach - Buffardi, Anne (Methods Lab, 2016)
Over the last half century, repeated calls for adaptive learning in development suggests two things: many practitioners are working in complex situations that may benefit from flexible approaches, and such approaches can be difficult to apply in practice. • Complexity thinking can offer useful recommendations on how to take advantage of distributed capacities, joint interpretation of problems and learning through experimentation in complex development programmes. • However, these recommendations rely on underlying assumptions about relationships, power and flexibility that may not hold true in practice, particularly for programmes operating in a risk averse, results-driven environment. • This paper poses guiding questions to assess the fit and feasibility of integrating complexity informed practices into development programmes.

Decision-Making and Data Use Landscaping [at DFID] - Powell, Josh; Orton-Vipond, Sarah; Bhatia, Vinisha; Kilroy, Annie (Development Gateway, 2018)
As DFID aims to harness the Data Revolution, ensuring that data1 drive decision-making, public accountability, and the achievement of the Sustainable Development Goals (SDGs), ensuring that systems, processes, and skills for data are aligned with these objectives is paramount. Across sector policy teams, country offices, and various analytical and technical cadres, different strengths and weaknesses, as well as needs and ambitions exist. To inform a strategic approach to data, as framed in its forthcoming Data Roadmap, DFID collaborated with Development Gateway to perform a Decision and Data Use Landscaping study. This report details lessons learned from approximately 60 interviews across 4 DFID country offices, all sector policy teams, senior managers, and various analytical and technical cadres and offices.

Adaptive programming in practice: shared lessons from the DFID-funded LASER and SAVI programmes - Derbyshire, Helen; Donovan, Elbereth (Synthesis Paper 3, 2016)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others).
Keywords: IMPORTANT; Practice

Impact evaluation for portfolio programmes on policy influence: Reflections on the Indonesian Poverty Reduction Support Facility - Mackenzie, Jessica; Hearn, Simon (Methods Lab, 2016)
• Donors are increasingly using portfolio-based programmes that embrace ‘good failure’ and adaptive, political programming. • However, measuring the impact of these programmes is challenging, especially for those working on policy influence and building country systems; not only do you need to measure the positive and negative impact of the overall portfolio, but also the different pathways tested. • Programmes, therefore, need a light-touch monitoring and evaluation system that allows it to remain flexible. • Good practice examples of portfolio-based programmes present six strategies to evaluate impact: 1. Develop appropriate logic models 2. Collect observational data throughout implementation 3. Develop stories of change or case studies 4. Understand causal relationships without a counterfactual 5. Purposefully select which activities to study 6. Be explicit about how impact will be valued across the portfolio. • These strategies are only useful if monitoring and evaluation is placed at the centre of programme decision-making.

The Limits of Institutional Reform in Development: Changing Rules for Realistic Solutions - Andrews, Matt (Cambridge University Press, 2013)
Institutional reforms are common across the globe. Think of efforts to build new governments in Afghanistan and Iraq; or decades worth of interventions intended to improve fiscal management, reduce corruption or introduce efficient public sector service delivery in African countries.These reforms often have limited results, however. They lead to new laws that are not properly implemented, and new organizations that have poor capacities and fail to function as needed. In this book, Matt Andrews explains why reform results are frequently limited and suggests ways to overcome these limits. In the first half of the book, Andrews argues that reforms fail to make governments better when they are introduced as signals to gain short-term support--from donors and others. Reforms as signals introduce unrealistic best practices that do not fit developing country contexts and are not considered relevant by implementing agents. The result is a set of new forms that do not function properly. Andrews uses examples to prove this point, ranging from efforts to introduce fiscal rules in Argentina to reforms aimed at international accounting standard adoption in many African countries, and anti corruption interventions in Malawi and Uganda. In the second half of the book, Andrews notes that there are instances where reforms are not being introduced as signals, and are having more of an impact on government effectiveness. Examples include local government reforms in Rwanda, anti corruption initiatives in Indonesia, and a variety of initiatives ranging from results based management to civil service modernization and internal control regime adoption in governments like Kenya, Kosovo and Afghanistan. Andrews uses these examples to discuss ways in which reforms can actually provide realistic solutions to governance challenges in developing countries. Lessons from these experiences suggest that reform limits can be overcome by focusing interventions on problem solving, and promoting incremental and localized processes to find solutions, involving multiple agents who can authorize and implement reforms.

The Politics of Evidence and Results in International Development: Playing the Game to Change the Rules? - Eyben, Rosalind; Guijt, Irene; Roche, Chris; Shutt, Cathy (Practical Action Publishing, 2015)
Understanding and demonstrating the effectiveness of efforts to improve the lives of those living in poverty is an essential part of international development practice. But who decides what counts as good or credible evidence? Can the drive to measure results do justice to and promote transformational change change that challenges the power relations that produce and reproduce inequality, injustice and the non-fulfillment of human rights? The Politics of Evidence in International Development provides a critical examination of the results agenda, with practical strategies for rendering it more helpful in supporting transformative development. The book deconstructs the origins and concepts of the results and evidence agendas employed in international development. It describes with concrete examples the current effects and consequences of the agenda, and goes on to outline a range of strategies used by individuals and organizations to resist, adapt or comply with the useful and problematic demands for results-oriented measurement and evidence of value for money."

Where have we got to on adaptive learning, thinking and working politically, doing development differently etc? Getting beyond the People’s Front of Judea - Algoso, Dave; Hudson, Alan (From Poverty to Power, 2016)
Dave Algoso and Alan Hudson at Global Integrity compare and contrast 9 different initiatives that are all heading in roughly the right direction in aid reform
Keywords: IMPORTANT

Valuing peace: delivering and demonstrating mediation results - Dilemmas & options for mediators - Wadley, Ian (Mediation Practice Series, 2017)
Essential points for practitioners and donors • Mediation offers a cost-effective and proven method for resolving armed conflict. Between 1985 and 2015, 75 per cent of armed conflicts in the world were resolved through agreement rather than by force. In most cases these processes will have involved third party facilitation or support. • Professional mediators understand the high stakes involved in their work to prevent, mitigate and resolve armed conflict. In addition, they and their financial supporters are increasingly required to demonstrate ‘value-for-money’ to ensure continued funding. • However, traditional monitoring and evaluation (M&E) methods are not well suited to this task, typically imposing artificially linear project models on a dynamic conflict situation, as well as compliance reporting that moves attention away from real value. • Traditional M&E methods tend to focus on documenting the past and generating vast amounts of data, rather than enabling timely adaptation of the project in the present. • Traditional M&E approaches rely heavily on external evaluation consultants. Even in the best of cases this may interfere with the mediation process and impose a heavy time burden on the project team, leading to low acceptance of traditional M&E approaches by mediation practitioners. • In contrast, an ideal M&E approach for mediation should deliver useful insights in even the most dynamic and sensitive mediation environments, impose a light reporting burden, and be readily accepted by mediation teams. It should protect discretion and trust, enable rapid adaptation, and also provide some assurance that donor funds are being well spent.

Assumptions, conjectures, and other miracles: The application of evaluative thinking to theory of change models in community development - Archibald, Thomas; Sharrock, Guy; Buckley, Jane; Cook, Natalie (Evaluation and Program Planning, 2016)
Unexamined and unjustified assumptions are the Achilles’ heel of development programs. In this paper, we describe an evaluation capacity building (ECB) approach designed to help community development practitioners work more effectively with assumptions through the intentional infusion of evaluative thinking (ET) into the program planning, monitoring, and evaluation process. We focus specifically on one component of our ET promotion approach involving the creation and analysis of theory of change (ToC) models. We describe our recent efforts to pilot this ET ECB approach with Catholic Relief Services (CRS) in Ethiopia and Zambia. The use of ToC models, plus the addition of ET, is a way to encourage individual and organizational learning and adaptive management that supports more reflective and responsive programming.
Keywords: Assumptions; Community development; Critical thinking; Evaluation capacity building; Evaluative thinking; International Development; Theory of change

Aid on the Edge of Chaos: Rethinking International Cooperation in a Complex World - Ramalingam, Ben (Oxford University Press, 2014)
It is widely recognised that the foreign aid system - of which every country in the world is a part - is in need of drastic overhaul. There are conflicting opinions as to what should be done. Some call for dramatic increases to achieve longstanding promises. Others bang the drum for cutting it altogether, and suggest putting the fate of poor and vulnerable people in the hands of markets or business. A few argue that what is needed is creative, innovative transformation. The arguments in Aid on the Edge of Chaos are firmly in the third of these categories. In this ground-breaking book, Ben Ramalingam shows that the linear, mechanistic models and assumptions that foreign aid is built on are more at home in early twentieth century industry than in the dynamic, complex world we face today. The reality is that economies and societies are less like machines and more like ecosystems. Aid on the Edge of Chaos explores how thinkers and practitioners in economics, business, and public policy have started to embrace new, ecologically literate approaches to thinking and acting, informed by the ideas of complex adaptive systems research. It showcases insights, experiences, and dramatic results of a growing network of practitioners, researchers, and policy makers who are applying a complexity-informed approach to aid challenges. From transforming approaches to child malnutrition, to rethinking process of macroeconomic growth, from rural Vietnam to urban Columbia, Aid on the Edge of Chaos shows how embracing the ideas of complex systems thinking can help make foreign aid more relevant, more appropriate, more innovative, and more catalytic. It argues that taking on these ideas will be a vital part of the transformation of aid, from a post-WW2 mechanism of resource transfer, to a truly innovative and dynamic form of global cooperation fit for the twenty-first century.

Accountability and Learning: Exploding the Myth of Incompatibility between Accountability and Learning - Guijt, Irene (NGO Management, 2010)
When accountability is understood as reporting on pre-deined deliverables, it is often considered to be irreconcilable with learning. This conventional wisdom inhibits an appreciation of their connection. In this chapter, Irene Guijt exposes the laws and traps in reasoning that keep accountability and learning apart. She provides practitioners with principles and basic good ideas that open up prospects for accountability and learning to complement each other.

Global governance and local peace: accountability and performance in international peacebuilding - Campbell, Susanna (Cambridge University Press, 2018)
Local peacebuilding and global accountability -- The country context--Burundi from 1999 to 2014 -- Ingos in peacebuilding--globally unaccountable, locally adaptive -- International organizations in peacebuilding--globally accountable, locally constrained -- Bilateral development donors--accountable for global targets, not local change

Politically smart approaches to donor investment climate programming. A Guidance Note - LASER (Synthesis Paper, 1, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Politically smart approaches to donor investment climate programming (and annexes) Revised February 2016 - sets out practical advice on how to adopt a politically smart (which requires being both ‘politically informed’ and ‘politically astute’) approach to programming. The annexes include a traffic light matrix for initial high level analysis; a problem diary template with examples; and an example of a flexible theory of change for adaptive, large scale programming
Keywords: Practice

The SAVI programme in Nigeria: Towards politically smart, locally led devlopment - Booth, David; Chambers, Victoria (ODI, 2014)
 More examples are needed of aid programming that works by being responsive to country realities: politically smart, problem-driven and locally led  DFID’s SAVI programme has revealed a hitherto untapped potential for change leading to better development results at state level in Nigeria  SAVI provides low-profile support to state-level organisations and partnerships, building their capacity to engage constructively with government  It avoid the pitfalls of a donor-driven approach by ‘taking the money off the table’  This illustrates the power of facilitated multi-stakeholder engagement and the disadvantages of seeing this in terms of ‘supply side’ and ‘demand side’ governance  The set-up of the DFID suite of state-level programmes, with separately managed sector support and ‘governance’ initiatives, has limited realisation of the potential  Key enabling conditions were that DFID provided space for an experience-based design process and permitted tangible results to be judged retrospectively, not pre-programmed

Thinking and Working Politically: Learning from practice. Overview to Special Issue - McCulloch, Neil; Piron, Laure-Hélène (Development Policy Review, 2019)
Over the last 15 years, a set of ideas now referred to as “thinking and working politically” (TWP) has coalesced into a “second orthodoxy” about how to take context into account when implementing development interventions. This approach stresses the importance of obtaining a better understanding of the local context (“thinking politically”) in order to support local actors to bring about sustainable developmental change (“working politically”). However, the evidence base to justify this new approach remains thin, despite a growing number of programmes which purport to be implementing it. Officials in development agencies struggle with putting it into practice and it is unclear how TWP differs—or not—from similar approaches, such as Problem Driven Iterative Adaptation (PDIA) and Doing Development Differently (DDD). This Special Issue sheds light on what TWP means in practice by examining a set of initiatives undertaken by both development partners and government departments in Nigeria, the Occupied Palestinian Territories, China and India. This overview article outlines, in brief, each of the Special Issue's four papers and then draws out five lessons—for funders and for practitioners—from across all the papers. Our five lessons are: (1) the fundamental importance of undertaking political economy analysis (PEA) to adapt programmes to their contexts; (2) the importance of having a realistic level of ambition for interventions; (3) the need to support local ownership—not just “agreement ownership” (between a donor agency and government) or local “management ownership” of the programme, but critically “driver ownership” by generating trust with the key local actors driving change; (4) the need for a more effective set of tools for measuring results in complex programmes that attempt to achieve improvements in long-run governance; and, (5) that although the political economy of donors is often seen as a barrier to applying TWP, the articles show how much can be done with a TWP approach if the analysis takes into account the political economy of donors as well as that of the local context. We conclude with a set of operational recommendations for donors and implementors, as well as suggestions of avenues for further research.
Keywords: Adaptation; Development programmes; Political economy analysis; Reform space; thinking and working politically

Managing Upward and Downward Accountability in an International Development Project - A Case Study of a World Bank Telecommunications Infrastructure Project in Benin - Kolker, Eva; Kulldorff, Catharina (Master's Thesis, Stockholm School of Economics, 2013)
Keywords: Downward accountability; Upward accountability

Overcoming Premature Evaluation - Roche, Chris (2016)
Guest post from Chris Roche on practical ways of introducing adaptive management, learning from failure etc in aid programmes

Guidance: Rigor and Reproducibility in Grant Applications | grants.nih.gov - NIH (National Institutes of Health, 2018)

The Implications of Complexity for Development - Barder, Owen (2012)
In this lecture, adapted from his May 2012 Kapuściński Lecture, Owen Barder explores the implications of complexity theory for development policy. He explains how traditional economic models have tried and failed to understand why some countries have managed to improve living standards while other countries have not.
Keywords: IMPORTANT

Rapid experiments with a purpose - Moses, Michael (BEAM Exchange, 2017)
New insights, opinions and perspectives on market systems development, from experts and practitioners.
Keywords: IMPORTANT

Black Box Thinking: The Surprising Truth About Success - Syed, Matthew (Hachette UK, 2015)
The Sunday Times No.1 Bestseller From the Bestselling Author of BounceWhat links the Mercedes Formula One team with Google?What links Team Sky and the aviation industry?What connects James Dyson and David Beckham?They are all Black Box Thinkers.Black Box Thinking is a new approach to high performance, a means of finding an edge in a complex and fast-changing world. It is not just about sport, but has powerful implications for business and politics, as well as for parents and students. In other words, all of us.Drawing on a dizzying array of case studies and real-world examples, together with cutting-edge research on marginal gains, creativity and grit, Matthew Syed tells the inside story of how success really happens - and how we cannot grow unless we are prepared to learn from our mistakes.
Keywords: Psychology; Sports & Recreation / Sports Psychology; Strategic Planning

Using what we know: How to ensure tech projects meet the brief - Walker, Tom (Making All Voices Count, 2017)
Making tech effective - building on what we already know

A ‘real-time’ and anthropological response to the Ebola crisis - IDS (IDS, 2017)
Impact Summary The Ebola epidemic that began in the Guinea-Sierra Leone-Liberia border region in December 2013 spread fast through the villages, cities and trade routes of this highly-peopled,...

Barrio Mio and Katye: PCI’s neighbourhood approach in cities - Campbell, Leah (AKNAP case study, 2019)

Assumption-aware tools and agency; an interrogation of the primary artifacts of the program evaluation and design profession in working with complex evaluands and complex contexts - Morrow, Nathan; Nkwake, Apollo M. (Evaluation and Program Planning, 2016)
Like artisans in a professional guild, we evaluators create tools to suit our ever evolving practice. The tools we use as evaluators are the primary artifacts of our profession, reflect our practice and embody an amalgamation of paradigms and assumptions. With the increasing shifts in evaluation purposes from judging program worth to understanding how programs work, the evaluator’s role is changing to that of facilitating stakeholders in a learning process. This involves clarifying purposes and choices, as well as unearthing critical assumptions. In such a role, evaluators become major tool-users and begin to innovate with small refinements or produce completely new tools to fit a specific challenge or context. We interrogate the form and function of 12 tools used by evaluators when working with complex evaluands and complex contexts. The form is described in terms of traditional qualitative techniques and particular characteristics of the elements, use and presentation of each tool. Then the function of each tool is analyzed with respect to articulating assumptions and affecting the agency of evaluators and stakeholders in complex contexts.
Keywords: Agency; Assumption-aware; Complex context; Complex programs; Participatory approaches; Program design; Program evaluation; Program tools; Theory-based

Is there a new Washington Consensus? An analysis of five World Development Reports - Evans, Alice (From Poverty to Power, 2017)
Is there a new Washington Consensus? Alice Evans analyses the last five World Development Reports and finds significant changes in orthodoxy, but also big gaps

Still watering white elephants? The blueprint versus process debate thirty years on - Booth, David (Perspectives on politics, production and public administration in Africa: essays in honour of Ole Therkildsen, 2015)

Impact assessment and the quest for the Holy Grail - Bymolt, Roger (KIT Working papers, 2015)

AID Programming Guide - DFAT (Australian Government, 2019)

Balancing Inclusiveness, Rigour and Feasibility: Insights from Participatory Impact Evaluations in Ghana and Vietnam - van Hemelrijck, Adinda; Guijt, Irene (Practice Paper, 2016)
This paper by Adinda Van Hemelrijck and Irene Guijt explores how impact evaluation can live up to standards broader than statistical rigour in ways that address challenges of complexity and enable stakeholders to engage meaningfully. A Participatory Impact Assessment and Learning Approach (PIALA) was piloted to assess and debate the impacts on rural poverty of two government programmes in Vietnam and Ghana funded by the International Fund for Agricultural Development (IFAD). We discuss the trade-offs between rigour, inclusiveness and feasibility encountered in these two pilots. Trade-offs occur in every impact evaluation aiming for more than reductionist rigour, but the pilots suggest that they can be reduced by building sufficient research and learning capacity.

PDIA Notes 2: Learning to Learn - Samji, Salimah (Building State Capability, 2016)
written by Peter Harrington After over two years of working with the government of Albania, and as we embark on a new project to work with the government of Sri Lanka, we at the Building State Capa…

Summarising portfolio change: results frameworks at organisational level - Simister, Nigel (M&E Paper 10, 2016)

Mission-Based Monitoring, Evaluation and Learning (MEL) Platforms Assessment Report - Arntson, Laura; Giannoni, Tonya; Peek, Nancy; Saarlas, Kristin (USAID, 2017)
In 2016, the Bureau of Policy, Planning and Learning (PPL) commissioned an internal stocktaking of USAID's mission-based MEL (Monitoring, Evaluation, and Learning) Platforms.

RFI-521-17-000015 - Improving Governance in Haiti Program (IGHI) - USAID (USAID, 2017)

Enabling citizen-driven improvement of public services. Leveraging Technology to Strengthen Accountability in Nigerian Healthcare - ICT4SA (World Bank and Reboot, 2015)
Effective public service delivery begins with knowing whether the services offered are working as intended. We launched a system to enable citizen input on the delivery of public services.

Innovation for International Development: Navigating the Paths and Pitfalls - Ramalingam, Ben; Bound, Kirsten (NESTA, 2016)
Experiences, insights and practical advice from over 20 leading practitioners in innovation for international development, brought together in one collection.

Utilization-Focused Evaluation (U-FE) Checklist - Patton, Michael Quinn (Evaluation Checklists Projects, 2013)
Utilization-Focused Evaluation begins with the premise that evaluations should be judged by their utility and actual use; therefore, evaluators should facilitate the evaluation process and design any evaluation with careful consideration of how everything that is done, from beginning to end, will affect use. Use concerns how real people in the real world apply evaluation findings and experience and learn from the evaluation process. The checklist is based on Essentials of Utilization-Focused Evaluation (Patton, 2012, Sage Publications). All references in the checklist to exhibits and menus refer to this book. Step 1 Assess and build program and organizational readiness for utilization-focused evaluation. Step 2 Assess and enhance evaluator readiness and competence to undertake a utilizationfocused evaluation. Step 3 Identify, organize, and engage primary intended users. Step 4 Conduct situation analysis with primary intended users Step 5 Identify primary intended uses by establishing the evaluation’s priority purposes. Step 6 Consider and build in process uses if appropriate. Step 7 Focus priority evaluation questions. Step 8 Check that fundamental areas for evaluation inquiry are being adequately addressed. Step 9 Determine what intervention model or theory of change is being evaluated. Step 10 Negotiate appropriate methods to generate credible findings and support intended use by intended users. Step 11 Make sure intended users understand potential controversies about methods and their implications. Step 12 Simulate use of findings. Step 13 Gather data with ongoing attention to use. Step 14 Organize and present the data for use by primary intended users. Step 15 Prepare an evaluation report to facilitate use and disseminate significant findings to expand influence. Step 16 Follow up with primary intended users to facilitate and enhance use. Step 17 Metaevaluation of use: Be accountable, learn, and improve

Taking responsibility for complexity: how implementation can achieve results in the face of complex problems - Jones, Harry (ODI, 2011)

Behavioral Design: A New Approach to Development Policy - Datta, Saugato; Mullainathan, Sendhil (Review of Income and Wealth, 2014)

Knowledge Retention and Transfer (KRT) - Model and Matsurity Matrix - USAID (CLA Toolkit, 2019)
The Maturity Matrix is not a standalone tool. It is one of the three major components of the KRT Model. The Maturity Matrix is meant to be used in conjunction with the KRT Toolkit and Implementation Plan.

The Boda Boda Talk Talk Module - Internews (Learning Collection, 2017)
Keywords: IMPORTANT

Evaluation of development programmes - OECD - OECD (2019)
Data & research on evaluation of development programmes inc. paris declaration, budget support, multilateral effectiveness, impact evaluation, joint evaluations, governance, aid for trade

Quality standards for development evaluation - OECD; Development Assistance Committee (OECD, 2010)
Based on a broad international consultative process, the DAC Quality Standards for Development Evaluation are a reference guide to good practice in development evaluation. With a view to improving the quality of evaluation processes and products, and facilitating collaboration, this reference guide lays out standards for each phase of a typical evaluation process: from defining purpose, to planning, designing, implementing, reporting, and learning from and using evaluation results.

Thinking and Working Politically in Economic Development Programmes – Some Sprints and Stumbles from a DFID Programme in Kyrgyzstan - Koleros, Andrew; Rinnert, David (From Poverty to Power, 2019)
A DFID programme in Kyrgyzstan offers useful insights into how the Thinking and Working Politically approach can escape from its governance ghetto
Keywords: Case Study

Program Cycle - How-To Note: Strategy-Level Portfolio Review - USAID (USAID PPL, 2017)

One step back, two steps forward: CARE’s journey towards doing development differently - Aston, Tom (Care Insights, 2017)
The Doing Development Different (DDD) community emerged in August 2014 and advocates that (a) the barriers to development are as much political as tec...

SAVI Approach Paper 1: Core Values - SAVI (London, 2015)
Governance reform is about government and citizens working together in more responsive, inclusive and accountable ways for the benefit of citizens. More responsive, inclusive and accountable attitudes and behaviour on the part of government and non-government stakeholders are the critical factors which lead to meaningful reform processes, and replicate and sustain reforms beyond the lifetime...

SAVI Approach Paper 2: Programme Design - SAVI (DFID, 2015)
SAVI supports citizen engagement in governance through a facilitated partnership approach, in contrast to the usual approach of grants to civil society organisations (CSOs). The overall aim is to facilitate and support working relationships and processes of reform that are home-grown, self-sustaining and, after initial engagement, not dependent on external support. Our way of working...

SAVI Approach Paper 3: Theory of Change - SAVI (DFID, 2015)
SAVI’s theory of change is a simple, practical guide that staff and partners use to plan and to monitor change – as well as to reflect on and enhance their own effectiveness. It sets out broad stages of attitude and behaviour change over time to facilitate effective citizen engagement in governance processes, systems and structures....

SAVI Approach Paper 6: Engaging Civil Society - SAVI (DFID, 2015)
SAVI state teams provide support to CS groups to become more effective agents of citizens’ voice and public accountability, through a variety of mutually reinforcing interventions. These include: hands-on support to demonstration civil society Advocacy Partnerships (APs) facilitating working partnerships between civil society APs, SHoAs, and the media brokering working relationships between all of these...

SAVI Approach Paper 7: Promoting Gender Equality and Social Inclusion - SAVI (DFID, 2015)
We promote attention to gender equality and social inclusion in all of our engagement with CS groups, the media and SHoAs, and in all of the issues and processes they work on. In all the states we work in, we also support partners to focus on some issues and form some partnerships and networks which...

SAVI Approach Paper 8: Engaging the Media - SAVI (DFID, 2015)
The overall aim of SAVI engagement with the media is for media representation of citizens’ interests to become normal, and play its part in helping state governments to be more responsive, inclusive and accountable to their citizens. Media partners – individual media personnel and selected media houses – are supported to be more effective agents...

SAVI Approach Paper 9: Engaging State Houses of Assembly - SAVI (DFID, 2015)
The overall aim of SAVI engagement with SHoAs is to promote lasting reforms that are not dependent on external funding and which promote an increasingly more responsive and accountable relationship between Nigerian state governments and their citizens. SHoAs are supported to be more effective agents of citizen voice and public accountability, demanding better performance from...

SAVI Approach Paper 10: Engaging State Governments - SAVI (DFID, 2015)
SAVI as a programme does not directly work with state governments – but we work in close conjunction with sister programmes who are supporting state governments on governance and sector reforms. SAVI supports non-government and SHoA partners to play their part in promoting more responsive, inclusive and accountable state governance delivering better services for citizens....

USAID ADS 201 - Program Cycle Operational Policy (Update 10/29/2018) - USAID (USAID, 2018)

ADS 201 Additional Help- Whole-of-Project Evaluation - USAID (USAID, 2017)

‘We have the solutions to our own problems’: supporting civil society in Nigeria - Overseas Development Institute (ODI, 2014)
Development assistance programmes that start from careful analysis of what works and what does not in country contexts are still remarkably rare. One reason for this is the lack of well documented examples of ‘politically’ smart aid programming. To this end, this film outlines the experience of the State Accountability and Voice Initiative (SAVI), a DFID-funded programme in Nigeria providing support to civil society, media and governmental organisations.

Program Cycle Road Map - USAID (2016)

Learning and Results in World Bank Operations: Toward a New Learning Strategy - World Bank (IEG , The World Bank, 2015)
This report is the second in a program of evaluations that the Independent Evaluation Group (IEG) is conducting on the learning that takes place through World Bank projects. Learning and knowledge are treated as parts of a whole and are presumed to be mutually reinforcing.
Keywords: IMPORTANT

Strategy Testing: An innovative approach to monitoring highly flexible aid programs - Ladner, Debra (Working Politically in Practice, 2015)
The international development community has increasingly embraced the idea that finding durable solutions to complex development problems requires new ways of working that move beyond industry norms. This paper makes an important contribution to the current debate by outlining an innovative monitoring system called Strategy Testing (ST). This is the third paper in the Working Politically in Practice paper series, launched together with the Australian Department of Foreign Affairs and Trade.

Effective Governance. Strategy for Australia’s aid investments - DFAT (Department of Foreign Affairs and Trade, Australian Government, 2015)

Forward Look - A vision for the World Bank Group in 2030 - World Bank (World Bank, 2016)

Strategic Framework for mainstreaming citizen engagemente in World Bank Group operations - World Bank (The World Bank, 2014)

Experiential Learning: Fostering lasting behavioural change - Norton, Brittney M. (Prospects practice paper, 4, 2016)
The term ‘experiential learning’ is often mistakenly used to describe any learning experience that involves participatory activities. This paper presents an overview of what true experiential learning is and how this form of learning allows for real-world application - thus promoting lasting behavioural change. Furthermore, it explains how experiential learning was adopted as the methodological core of the Prospects psychosocial programme in Liberia, which builds ‘pre-employment skills’ in 3,500 vulnerable youth aged 15-24 years. The goal of the paper is to provide other youth and education development practitioners with a resource that can be used to strengthen youth and behaviour change programmes through the incorporation of the experiential learning theory. In addition, this paper explains its application in the Prospects programme, before concluding with key considerations of such a design. 1

Failing Forward: How CARE is focusing on what goes wrong to improve impact - Janoch, Emily (2019 CLA Case Competition, 2019)
CARE's Failing Forward initiative is sparking opportunities to showcase the ideas that don't work so we can spend more time implementing the ones that do. It's changing the conversation inside the organization, and leading to changes in the way we design and implement programs. It's also allowing us to make connections across a global portfolio of more than 900 projects, and with new and different partners to learn from their experience.

Forget the money: De-linking technical assistance - Manuel, Clare (Synthesis Paper, 4, 2016)

Introduction to SAVI's way of working - State Accountability and Voice Initiative (SAVI) - SAVI (DFID, 2015)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact.  SAVI Approach Papers summarise key aspects of SAVI’s way of working. They explain what we do, and why – and link to relevant tools and frameworks. Our approach is summarized in...
Keywords: Practice

State Accountability and Voice Initiative (SAVI) - Approach Paper Series - SAVI (DFID, 2016)
We are piloting a new approach to identifying and supporting our partners.  This breaks with convention in many ways in order to improve impact. Our approach is summarized in the Introduction to SAVI’s way of working. We have broken our approach down into key components – depicted in the form of our ‘knowledge tree’ –...
Keywords: IMPORTANT

Bringing Participation into Complexity-Aware MEL: What is the evidence? - Apgar, Marina; Higdon, Grace Lyn (2018)

It's All About MeE: Using Structured Experiential Learning (“e”) to Crawl the Design Space - Pritchett, Lant; Samji, Salimah; Hammer, Jeffrey (Working Paper 322, 2013)
This paper argues that within-project variations in design can serve as their own counterfactual, reducing the incremental cost of evaluation and increasing the direct usefulness of evaluation to implementing agencies. It suggests combining monitoring (‘M’), structured experiential learning (‘e’), and evaluation (‘E’) so as to facilitate innovation and organisational capability building while also providing accountability …

Supporting Learning? Exploring the relationship between grantee learning and grantmaking practice in the transparency and accountability sector - Ross, Jenny (INTRAC, 2015)
Learning is fundamental to work on transparency and accountability in complex environments. But how can funding practices best support learning?

Virtuous cycles of learning: Using formative, embedded, and diagnostic developmental assessments in a large-scale leadership program - Stein, Z.; Dawson, Theo; Van Rossum, Zachary; Rothaizer, Joel; Hill, S. (Journal of Integral Theory and Practice, 2014)
This article presents preliminary results from a series of ongoing action-research projects involving the use of embedded diagnostic developmental assessments (called LectaTests™) in leadership education contexts. These findings are presented to support a particular metatheoretical approach to learning and education in which embedded assessments form a crucial part of ongoing virtuous cycles of action, feedback, support, and learning. We present two types of evidence. First, we compare developmental growth across eight program evaluations in which LectaTests were and were not embedded. Second, we examine how embedding LectaTests in a large-scale leadership development program affected the growth of managers and their direct reports. We review these findings with an eye toward detecting the benefits of using developmental assessment as embedded diagnostics alongside their use as research instruments. We begin by using Integral Theory to structure a discussion about the ideal function of developmental assessments in educational contexts.

What can the Thinking and Working Politically community learn from peace and conflict mediation? - Douglas, Alex (From Poverty to Power, 2018)
Wily aid practitioners have long understood the importance of adapting their programs to the political environment, and even use their activities to push politics in a progressive direction. But this magic was spun secretly, hidden behind logframes and results frameworks. Only recently has a range of programs been permitted to escape the dead hand of technocracy. But there was one corner of the development and humanitarian world that never needed to shroud its political ambitions; those of us working on resolving violent conflicts. Donors have always understood our work could never be disembodied from politics. This field included elements of the UN, regional organisations, and NGOs, such as the one I work for: the Centre for Humanitarian Dialogue. With a new focus on development being enabled by a series of ‘deals’ between different actors, it seems timely to examine the strategies used to reach peace agreements and whether they contain broader lessons for TWP/DDD/Adaptive Management.

Teams that Do Development Differently - Khan, Jehanzeb; Fisher, Annette (Global Policy Journal, 2017)

SAVI Approach Paper 13: Measuring Value for Money and using Value for Money Analysis - SAVI (DFID, 2016)
SAVI has established its own framework for assessing Value for Money in annual performance – in relation to expenditure, economy, efficiency, effectiveness and equity. Routine tracking and analysis of expenditure and economy ensure that inputs are supplied and services delivered to partners in line with SAVI’s core values, whilst also meeting DFID requirements and competing...

Scenario-based strategizing: Advancing the applicability in strategists' teams - Lehr, Thomas; Lorenz, Ullrich; Willert, Markus; Rohrbeck, René (Technological Forecasting and Social Change, 2017)
For over 40years, scenarios have been promoted as a key technique for forming strategies in uncertain environments. However, many challenges remain. In this article, we discuss a novel approach designed to increase the applicability of scenario-based strategizing in top management teams. Drawing on behavioural strategy as a theoretical lens, we design a yardstick to study the impact of scenario-based strategizing. We then describe our approach, which includes developing scenarios and alternative strategies separately and supporting the strategy selection through an integrated assessment of the goal-based efficacy and robustness. To facilitate the collaborative strategizing in teams, we propose a matrix with robustness and efficacy as the two axes, which we call the Parmenides Matrix. We assess the impact of the novel approach by applying it in two cases, at a governmental agency (German Environmental Ministry) and a firm affected by disruptive change (Bosch, leading global supplier of technology and solutions).
Keywords: Behavioural strategy; Scenario-based strategizing; Scenarios; Strategic foresight; Uncertainty

Strengthening Advocacy and Civic Engagemetn in Nigeria - Chemonics (Chemonics International, 2018)

The Future is a Choice: The Oxfam Framework and Guidance for Resilient Development - Jeans, Helen; Thomas, Sebastien; Castillo, Gina (Policy & Practice, 2016)
This guide provides a framework for Oxfam staff to design programmes and campaigns that contribute to resilient development. Oxfam defines resilience as ‘the ability of women and men to realize their rights and improve their well-being despite shocks, stresses

Naturalizing sensemaking - Snowden, Dave (Informed by Knowledge: Expert Performance in Complex Situations, 2010)
The focus of this book is on how experts adapt to complexity, synthesize and interpret information in context, and transform or "fuse" disparate items of information into coherent knowledge. The chapters examine these processes across experts (e.g. global leaders, individuals in extreme environments, managers, police officers, pilots, commanders, doctors, inventors), across contexts (e.g. space and space analogs, corporate organizations, command and control, crisis and crowd management, air traffic control, the operating room, product development), and for both individual and team performance. Successful information integration is a key factor in the success of diverse endeavors, including team attempts to climb Mt. Everest, crowd control in the Middle East, and remote drilling operations. This volume is divided into four sections, each with a specific focus on an area of expert performance, resulting in a text that covers a wide range of useful information. These sections present well-researched discussions, such as: the management of complex situations in various fields and decision contexts; technological and training approaches to facilitate knowledge management by individual experts and expert teams; new or neglected perspectives in expert decision making; and the importance of ‘modeling’ expert performance through techniques and frameworks such as Cognitive Task Analysis, computational architectures based on the notion of causal belief mapping such as ‘Convince Me,’ or the data/frame model of sensemaking. The volume provides essential reading for researchers and practitioners of Naturalistic Decision Making and those who study Expertise; Organizational and Cognitive Psychologists; and researchers and students in Business and Engineering.

The Clash of the Counter-bureaucracy and Development - Natsios, Andrew (The Center for Global Development, 2010)
In this essay, Andrew Natsios gives a first-hand account of what he finds most hinders USAID—layers of bureaucracy that misguide and derail development work.

Evaluating Complexity. Propositions for improving practice - Preskill, Hallie; Gopal, Srik (FSG, 2014)
9 propositions can help evaluators measure progress on complex social problems.
Keywords: IMPORTANT

How Does the World Bank Build Citizen Engagement Commitments into Project Design? Results from Pilot Assessments in Mozambique, Myanmar, Nigeria, and Pakistan - Nadelman, Rachel; Le, Ha; Sah, Anjali (Working Paper 525, 2019)
How and to what degree is the World Bank putting its new institutional citizen engagement (CE) commitments into practice? This question guides an independent assessment that the Accountability Research Center (ARC) at American University has undertaken as part of the Institute of Development Studies-led Action for Empowerment and Accountability (A4EA) research programme’s investigation into how external actors can best support local processes of and conditions for empowerment and accountability. This report investigates the World Bank’s incorporation of CE into project design, the critical early stage of donor engagement. To accomplish this, ARC reviewed the World Bank’s fiscal year 2015–17 investment project portfolios for four A4EA priority countries, Mozambique, Myanmar, Nigeria, and Pakistan, which covers 57 projects that range from US$19 million to U$600 million. The analysis determines whether projects commit to seeking a strategic approach to CE, which involves combining multiple tactics so that the whole could be greater than the sum of the parts. This assessment of CE commitments is intended to help to inform possible national, civil society organisation strategies to monitor whether and how these commitments are actually implemented in practice.

Strategies for learning from failure - Edmondson, Amy C. (Harvard Business Review, 2011)

Thinking and Working politically to support developmental leadership and coalitions: The Pacific Leadership Program - Denney, Lisa; McLaren, Rebecca (Research Paper, 2016)

How DFID learns - ICAI (Independent Commission for Aid Impact (ICAI), 2014)
Excellent learning is essential for UK aid to achieve maximum impact and value for money. We take learning to mean the extent to which DFID uses information and experience to influence its decisions. Each ICAI review assesses how well learning takes place. Our reports to date indicate a mixed performance. This review seeks to identify the way DFID learns and what inhibits it from doing so consistently. We drew on our reviews, assessed data from DFID’s own surveys and carried out interviews inside and outside the department. Review DFID generates considerable volumes of information, much of which, such as funded research, is publicly available. DFID does not clearly or consistently link this investment to how it can deliver better impact. We made five recommendations and gave an amber-red score. Findings DFID does not clearly identify how its investment in learning links to its performance and delivering better impact. DFID has the potential to be excellent at organisational learning if its best practices become common. DFID staff learn well as individuals. They are highly motivated and DFID provides opportunities and resources for them to learn. DFID is not yet, however, managing all the elements that contribute to how it learns as a single, integrated system. DFID does not review the costs, benefits and impact of learning. Insufficient priority is placed on learning during implementation. The emphasis on results can lead to a bias to the positive. Learning from both success and failure should be systematically encouraged. Recommendations DFID needs to focus on consistent and continuous organisational learning based on the experience of DFID, its partners and contractors and the measurement of its impact, in particular during the implementation phase of its activities. All DFID managers should be held accountable for conducting continuous reviews from which lessons are drawn about what works and where impact is actually being achieved for intended beneficiaries. All information commissioned and collected (such as annual reviews and evaluations) should be synthesised so that the relevant lessons are accessible and readily usable across the organisation. The focus must be on practical and easy-to-use information. Knowhow should be valued as much as knowledge. Staff need to be given more time to acquire experience in the field and share lessons about what works and does not work on the ground. DFID needs to continue to encourage a culture of free and full communication about what does and does not work. Staff should be encouraged always to base their decisions on evidence, without any bias to the positive.

NGOs Doing Development Differently - Green, Duncan (From Poverty to Power, 2017)
Report back from a meeting of international NGOs to set up a research and practice network on 'Doing Development Differently' that can complement other actors

Release the pressure on governance practitioners - de Weijer, Frauke; Hauck, Volker (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Improving development aid design and evaluation: Plan for sailboats, not trains - Kleinfeld, Rachel (Carnegie Endowment for International Peace, 2015)
How do reforms that require political engagement differ from traditional technical reforms? Why is political engagement different, and what are the implications for design and evaluation? How should development programmes that engage politics be designed? And how can those who fund or implement such programmes evaluate whether their efforts are contributing to reform? This report …
Keywords: IMPORTANT

Measuring Impact. Making Use of the Portfolio: Organizational Learning at USAID - Peabody, Shawn (Measuring Impact, 2015)
This technical analysis explores previous and ongoing social learning efforts, best practices, challenges, and lessons in USAID as a foundation for improving the implementation and design of the Agency’s forestry and biodiversity programs. This analysis is particularly relevant as the Bureau of Economic Growth, Education and the Environment’s Office of Forestry and Biodiversity (E3/FAB) begins to develop a Cross-Mission Learning Program under the Measuring Impact initiative, a five-year activity to promote the adoption of best practices in the USAID program cycle among Missions using biodiversity funds. The findings reported in this document can help inform the overall design and structure of the Learning Program and provide insight into possible challenges and best practices.

Local Systems: a framework for supporting sustained development - USAID (USAID, 2014)

How We Model Matters: A Manifesto for the Next Generation of Program Theorizing - Whynot, Jane; Lemire, Sebastian; Montague, Steve (Canadian Journal of Program Evaluation, 2019)
In this concluding article, grounded on the exemplary contributions contained in the preceding pages, the guest editors scale the proverbial soapbox and present a manifesto to guide the pursuit and advancement of the next generation of program theorizing. Formulating ten declarations for program theory development and examination, the modest hope of the authors is to motivate and inspire reflective evaluation practitioners to broaden their views, approaches, and techniques for future program theorizing.

Two Tunes, One Dance: Keeping Programming Agile - Learning Lab (USAID Learning Lab, 2017)

World Development Report 2017: Governance and the Law - World Bank (The World Bank, 2017)

Everyday Political Analysis - Hudson, David; Marquette, Heather; Waldock, Sam (Developmental Leadership Program, 2016)
This short note introduces a stripped-back political analysis framework designed to help frontline development practitioners make quick but politically-informed decisions. It aims to complement more in-depth political analysis by helping programming staff to develop the 'craft' of political thinking in a way that fits their everyday working practices. Everyday Political Analysis involves two steps: Understanding interests: What makes people tick? Understanding change: What space and capacity do people have to effect change? For each step five questions, accompanied by prompts, aim to help staff to conduct quick political analysis. The EPA framework can be used at any stage of the aid management cycle, and can help users to respond rapidly to unexpected change. We are keen to hear back from people on their experience of using EPA to help us adapt the framework. Was it useful (or not)? Do people tend to use just one or both steps? Are there missing statements or prompts that would improve the analysis? Please email us at info [at] dlprog.org.

Thinking and Working Politically – Are We Seeing the Emergence of a Second Orthodoxy? - Teskey, Graham (Governance Working Paper 1, 2017)
There now is a persuasive volume of evidence that demonstrates that capacity and technical knowledge alone are insufficient to change deeply entrenched political interests and bureaucratic norms. These critiques demonstrate that an understanding of power asymmetries is frequently the critical missing ingredient in project design and implementation. Many eminent thinkers have looked at the difference between success and failure in development, and all point to the primacy of domestic politics. This point has not been lost on development agencies and some have tried to provoke greater attention to the role that politics plays. However, this recognition is yet to pass into the mainstream of development practice. Despite the slow but sure accretion of this knowledge the international community seems to be wedded to doing development traditionally. The purpose of this paper is to consider the extent to which a ‘second orthodoxy’ is slowly emerging which can stand alongside, and in some cases may supplant, the ‘first orthodoxy’ of the traditional project framework. Care has to be taken in making this argument, as there is certainly no consensus within the development community on its importance, and even among advocates, there are slightly differing interpretations of what this second orthodoxy looks like. Further, it is not absolutely clear that the two orthodoxies can co-exist. The paper does not call for any ‘paradigm shift’ in how development practitioners conceptualise programs and projects, nor does it demand that the project framework be scrapped; the former would be impossible and the latter undesirable. Equally readers will find no claims that Doing Development Differently or ‘Thinking and Working Politically’ will always and everywhere guarantee better development outcomes. Rather, the paper seeks to summarise how the two orthodoxies differ, where the second orthodoxy now stands, and propose how it can be taken forward in practical terms.

From best practice to best fit: understanding and navigating wicked problems in international development - Ramalingam, Ben; Laric, Miguel; Primrose, John (Working Paper, 2014)

Putting theory into practice: how DFID is doing development differently - Wild, Leni; Booth, David; Valters, Craig (ODI, 2017)
Keywords: IMPORTANT

Navigating by Judgment: Organizational Structure, Autonomy, and Country Context in Delivering Foreign Aid - Honig, Daniel (Harvard University, Graduate School of Arts & Sciences, 2015)
This dissertation examines when initiatives by International Development Organizations (IDOs) are more, and less, successful. The core argument is that allowing field-level agents to drive initiatives – what I call organizational Navigation by Judgment – will often be the most effective way to deliver aid. This inverts what a classical application of the principal agent model – the workhorse of studies of public management and bureaucracy – would predict, with better performance resulting from less control. In the delivery of foreign aid the costs of monitoring to the principal are often overshadowed by the deleterious effects of the monitoring itself. The core of the argument is that development implementation requires soft information, tacit knowledge, and flexibility that are crowded out by tight controls or an organizational navigation strategy focused on short term measurement and targets. As a result there are increasing returns to Navigation by Judgment in environments that are uncertain or difficult to understand from the outside and tasks where outputs are difficult to observe and/or poorly correlated with long term intervention goals. Insecure political authorizing environments which constrain the autonomy of IDOs prevent these organizations from Navigating by Judgment in situations where this is the best strategy. Empirically, this dissertation examines a cross-IDO dataset of projects (including over 14,000 projects over 50 years over 9 organizations), which I have assembled. It also examines eight cases of development interventions in Liberia and South Africa. These cases are matched pairs comparing the performance and navigation strategies of the US Agency for International Development (a low autonomy IDO) and the UK’s Department for International Development (a higher autonomy IDO) in capacity building and health sector interventions.
Keywords: IMPORTANT

Monday morning in Kigali: what do you do when you get off the plane? Practical guidance for PDIA practitioners - LASER (Synthesis Paper, 1, 2016)
In order to help enhance the effectiveness of donors and development practitioners on the ground, LASER has produced a range of practical guidance and tools. These are primarily intended for the international development community engaged in designing and implementing investment climate programmes, though can also be used more widely by other stakeholders across sectors. General guidance and tools: Monday morning in Kigali January 2016 - what do you do when you get off the plane? Practical guidance for PDIA practitioners
Keywords: IMPORTANT; Practice

Investment Climate Reform: Doing it Differently - Manuel, Clare (Synthesis Paper, 1, 2015)
LASER synthesis papers aim to help donors and other stakeholders better understand why and how to approach investment climate reform programming differently. The papers reflect emerging best practice and lessons learnt on what works and what does not work in doing development differently. The papers have been peer-reviewed by experts in the field including senior advisers at DFID, World Bank, IFC and the Donor Committee for Enterprise Development (amongst others). First synthesis paper - Investment climate reform: doing it differently June 2015 Drawing on our experience in taking a problem-focused approach to investment climate reform, we discuss in this peer-reviewed paper emerging lessons and reflections on what works, both in recent literature and in practical experience.

DFID Smart Rules: Better Programme Delivery - version VII (2017.04) - DFID (DFID, 2017)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

A Governance Practitioner’s Notebook: Alternative Ideas and Approaches - Whaites, Alan; Gonzalez, Eduardo; Fyson, Sara; Teskey, Graham (OECD, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

DFID Smart Rules: Better Programme Delivery - version VI (2016.10) - DFID (DFID, 2016)
Smart Rules provide the operating framework for the Department for International Development’s (DFID’s) programmes.
Keywords: IMPORTANT; Practice

SAVI Approach Paper 4: Thinking and Working Politically - Supporting partners and staff through a participatory apporach to political economy analysis - SAVI (DFID, 2015)
Thinking and acting politically is central to the SAVI programme. We support staff and partners to analyse the power relations that shape change in their state, and to use this knowledge to inform their decision-making. This includes decisions made by SAVI state teams relating to the issues and partners they engage with and support, and...

Design thinking: understand - improve - apply - Plattner, Hasso; Meinel, Christoph; Leifer, Larry (Understanding innovation, 2011)
"In this book, the researchers take a system's view that begins with a demand for deep, evidence-based understanding of design thinking phenomena. They continue with an exploration of tools which can help improve the adaptive expertise needed for design thinking. The final part of the book concerns design thinking in information technology and its relevance for business process modeling and agile software development, i.e. real world creation and deployment of products, services, and enterprise systems"--Cover
Keywords: Creative ability in business; Creative thinking; Designer; Industrial management; Innovation; Organizational change; Product development; System design; Technological innovations

It's the politics! Can donors rise to the challenge? - Unsworth, Sue (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Doing Development Differently at the World Bank: updating the plumbing to fit the architecture - Bain, Katherine A.; Booth, David; Wild, Leni (ODI, 2016)
Keywords: IMPORTANT

Case study: Embedding reform and exiting: LASER’s application of the hourglass approach to achieve sustainable results - Manuel, Clare (DFID-LASER Programme, 2016)
This case study describes how LASER has gone about enabling systemic change and sustainable uptake of reforms that address complex institutional problems in Kenya, Rwanda, Sierra Leone, Somaliland and Uganda. In each of these countries LASER has designed-in a sustainable approach from the start based on: (i) local ownership and leadership of reforms based on developing country (rather than donor) priorities; (ii) use of country (rather than donor programme) systems; and (iii) an understanding that the role of the donor / development practitioner is to support (rather than buy) reform. The case study uses LASER’s hour glass methodology, illustrated with examples from LASER interventions, to show how these principles guide LASER operations every step of the way.
Keywords: IMPORTANT; Practice

Simplexity² or: How I Learned to Stop Worrying and Love Complexity in Development - Prieto Martin, Pedr (Complexity and Development Seminar Series, 2018)
This seminar is the fifth in a series that aims to share cutting edge thinking and research being done at IDS and the University of Sussex around how we practically capture and account for complexity across a variety of sustainable development contexts. Join us for a fascinating trip from Athens to Xiaogang where, assisted by Steve Jobs, Sun Tzu and Aristotle, and with the help of a series of memorable diagrams, we attempt to alchemise development’s complexity into… a simple living tree. The seminar aims to integrate into an accessible narrative notions from various disciplines related to complexity science –including psychology, philosophy, organisational development and software engineering– as a way to articulate essential complexity concepts. Insights emerging from our cluster’s research on Adaptive Management and on the use of Frontier Technologies for development are linked with ideas presented by Prof. Chambers, Burns, Scoones and Ang in the previous seminars, to explore what complexity means in practice for development professionals and how we can discern and handle it at best. About the Speaker Pedro Prieto Martín is a software engineer turned trans-disciplinary social scientist. Pedro’s academic background includes degrees in Computer Science, Business Administration, Philosophy, and Sociology from different Spanish universities. After working for years at Hewlett-Packard in Germany as the Technical Lead of a development team, he moved to Latin America, where for years he researched the application of ICT to improve local governance and promote social change. Before joining the Digital and Technology cluster he supported and researched, at the local level, the social mobilisation processes that resulted from the “indignados” movement in Spain and their use of ICT. At IDS, Pedro has investigated the drivers of adaptiveness in accountability interventions, as part of MAVC. He now coordinates the learning component of DFID’s “Frontier Technologies Livestreaming (FTL)” programme, which has been recently awarded UK’s Civil Service Award for Innovation. FTL supports DFID country offices to experiment with the use of emerging technologies to address development challenges.

Scaling Up Inclusive Approaches for Marginalised and Vulnerable People - Carter, Becky; Joshi, Anu; Remme, Michelle (2018)
This rapid review summarises the evidence on how to scale up inclusive approaches to complex social change. It looks at how to design scalable inclusive change interventions, as well as how to plan and manage the scale-up process. Focusing on interventions with the aim of reaching the most marginalised and transform social norms, it covers programmes aiming to deliver inclusive outcomes for women and girls (with a particular focus on preventing violence against women and girls) and persons with disabilities. To date, many interventions seeking to change harmful gender and disability norms have been implemented as small-scale projects. There are limited experiences of scale-up and fewer evaluations of these experiences. However, there are some documented case studies as well as emerging analysis that draw out lessons learned. From this evidence base, this rapid desk review identifies eight critical issues commonly highlighted as important considerations when scaling up inclusive change interventions: 1. Opportunities for systemic approach, including integrating political and community-level scale-up, and coordinating across multiple sectors and stakeholders 2. Political support for scale-up 3. Strategic choices: balancing reach, speed, cost, quality, equity, and sustainability 4. Catalysing change: tipping points, diffusion effects, and local champions 5. Locally grounded, participatory, and adaptive approaches 6. Long-term approaches with funding models to match 7. Cost-effective and financially feasible scale-up strategies 8. Measuring impact and sustainability.

Mind the gaps: What's missing in political economy analysis and why it matters - Hudson, David; Marquette, Heather (A Governance Practitioner’s Notebook: Alternative Ideas and Approaches, 2015)
The Governance Practitioner’s Notebook takes an unusual approach for the OECD-DAC Network on Governance (GovNet). It brings together a collection of specially written notes aimed at those who work as governance practitioners within development agencies. It does so, however, without attempting to offer definitive guidance – instead aiming to stimulate thinking and debate. To aid this process the book is centred on a fictional Governance Adviser. The Notebook’s format provides space for experts to speak on today’s governance issues: politics, public sector reform and stakeholder engagement. It encourages debate, charts the evolution of donor thinking, and highlights future challenges in the age of the Sustainable Development Goals. Each section introduces both technical issues and major areas of debate, providing ideas for future development support to institutional reform.
Keywords: IMPORTANT

Theory of Change Thinking in Practice - van Es, Marjan; Guijt, Irene; Vogel, Isabel (2015)
Want to know better how your interventions can contribute to change? A Theory of Change (ToC) approach helps in deepening your understanding - and that of your partners - of how you collectively think change happens and what the effect will be of your intervention. Not only does it show what political, social, economic, and/or cultural factors are in play, it also clarifies your assumptions. Once a ToC has been developed, it can be used to continually reflect on it in ways that allow for adaptation and checking of assumptions of your intervention. This user friendly guideline helps you to use a Theory of Change approach. Theories of change are the ideas and beliefs people have – consciously or not – about why and how the world and people change. How people perceive and understand change and the world around them is infused by their underlying beliefs about life, human nature and society. They are deep drivers of people’s behaviour and of the choices they make. Social change processes are complex and characterised by non-linear feedback loops: our own actions interact with those of others and a myriad of influencing factors. This triggers reactions that cannot be foreseen and makes outcomes of change interventions unpredictable. Given these uncertainties, how can we plan strategically and sensibly? How can social change initiatives move forward in emerging change processes in a flexible way, while remaining focused on the goal? In this context of complexity, Hivos has found a theory of change (ToC) approach useful in guiding its strategic thinking and action, as well as its collaborative efforts with others. As it fosters critical questioning of all aspects of change interventions and supports adaptive planning and management in response to diverse and quickly changing contexts. It contributes to the quality and transparency of strategic thinking, and therefore to personal, organisational and social learning. This guide builds on the experiences of Hivos working with a ToC approach. It is a practical guide for Hivos staff in applying a Theory of Change approach, but is also very useful for others working on social change such as social entrepreneurs and innovators. This guide builds on the work of a ToC Learning Group initiated by Hivos and comprising of staff of the Centre for Development Innovation (CDI) of Wageningen University and Research Centre and of experts Iñigo Retolaza Eguren, Isabel Vogel and Irene Guijt. For current thinking and work on the use of Theory of Change thinking in complex change processes, see http://www.theoryofchange.nl

SPACES MERL: Systems and Complexity White Paper - USAID (2016)
The Strategic Program for Analyzing Complexity and Evaluating Systems (SPACES MERL) project is an activity funded by USAID’s Global Development Lab and the Bureau for Policy, Planning and Learning (PPL). This three-year activity aims to bring a variety of tools and methodologies that decision-makers can use (alone or in combination) to provide comprehensive systems analysis. The activity is being implemented from 2015 to 2018 by a consortium of organizations expert in systems and complexity, including the Global Obesity Prevention Center (GOPC) at Johns Hopkins University (Prime), Global Knowledge Initiative (GKI), LINC and ResilientAfrica Network (RAN). This Systems and Complexity White Paper is a collaborative effort of the SPACES MERL team, designed to frame the international development landscape, with particular reference to USAID-funded activities, for application of systems and complexity approaches to design, monitoring and evaluation. Customized to the systems and complexity layperson with in-depth knowledge of international development practice, the objectives of this white paper are three-fold:  Provide an overview of systems and complexity practice, its current state of application and relevance to international development practice;  Establish a taxonomy of systems and complexity tools, highlighting the fit of those offered by SPACES MERL within the wider landscape; and  Review and provide information on application of SPACES MERL tools, their purpose and construction, required data, and their applicability to specific contexts.